Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Genomic and food-safety evaluation of Staphylococcus chromogenes in Chinese dairy milk - Xiaoping Li; Baoling Zhang; Tao Zhou; Moli Li; Kai Chen; Shu Li; Xiaofang Tong; Herman W. Barkema; Diego B. Nobrega; John P. Kastelic; Yuqiong Li; A Yao; et al. (Food Research International, 2026)

Hydrogen bond-assisted rapid ammonium ion transport in Prussian blue electrochromic devices - Bingkun Huang; Feifei Zhao; Long Zhang; Yukai Xu; Jiashuo Li; Qilin Wei; Xinxin Han; Litao Kang; Jia-Yue Yang; Wu Zhang; Jingwei Chen; William W. Yu (Chemical Engineering Journal, 2026)

Clinical outcomes of patients with brain metastases from primary esophageal cancer - Bianca Nolde-Lopez; Christina K. Cramer; Scott Isom; Anthony Naquin; Caio M.S.P. Rocha Lima; Ravi K. Paluri; Jimmy Ruiz; Fei Xing; Christopher T. Whitlow; Stephen B. Tatter; Adrian W. Laxton; Jaclyn J. White; et al. (Next Research, 2026)

Adaptive seasonal management after eradicating invasive Spartina: A nature-based approach - Dong-Fan Xu; Qi Yuan; Hai-Qiang Guo; Bing Tan; Fei Quan; Zhe-Xiu Yu; Dong-Yang Han; Yu-Jiao Lu; Ying-Ying Hao; Si-Qi Zhou; Guang Ge; Bin Zhao; et al. (Ecological Engineering, 2026)

Correction: Two-year field testing of genetically engineered American chestnut reveals fungal blight tolerance - Thomas Klak; Steven E. Travis; Virginia Grace May; Ek Han Tan; Matthew W. H. Chatfield; Miranda Wheeler (New Forests, 2026)

Funnel-bottom smart pond engineering reduces dissolved inorganic nitrogen accumulation in intensive shrimp culture - Hsueh-Han Hsieh; W. Sanjaya Weerakkody; Pin-Chun Liu; Ing-Jer Huang; Chin-Chang Hung (Aquacultural Engineering, 2026)

Morphology and Phylogeny of Hyalinostachys dehongensis sp. nov., a Bambusicolous Species From Yunnan Province, China - Yu‐Rong Yan; Li‐Su Han; Gang‐Ya Xu; Samantha C. Karunarathna; Nakarin Suwannarach; Jaturong Kumla; A. N. W. Sumedha Thushari; Sajad Ali; Dong‐Qin Dai; Saowaluck Tibpromma (New Zealand Journal of Botany, 2026)
China has abundant bamboo resources, among which Yunnan Province is one of the regions with the greatest number of species. The unique natural and geographic advantages provide an excellent environment for fungal growth. This study collected and isolated saprobic hyphomycetes associated with dead bamboo in Yunnan Province, China. Based on detailed morphological comparisons and multi‐locus phylogenetic analyses of combined LSU, ITS, tef 1‐ α , rpb 2, tub 2, and cmdA sequence data, the new isolates are introduced here as a novel species, Hyalinostachys dehongensis in the family Stachybotryaceae of Ascomycota. A complete description, morphological illustrations, and phylogenetic analysis results for the new species are provided. In addition, this species is introduced here as the second species since this genus was introduced in 2020.

Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

Development of a multi-criteria indicator for product life cycle decision-making - Yong Han Kim; Sidi Deng; Thomas Maani; Matthew J. Triebe; Nehika Mathur; John W. Sutherland (Journal of Cleaner Production, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Amine-functionalized cellulose fiber sorbents via solvent-tuned aminosilane grafting for direct air capture - Ahhyun Roh; Jun Hyoung Lee; Euno Doo; Min-Kyung Kim; Jae-Cheol Lee; Jinmo Park; Jihye Lee; Yo-Han Kim; Jae W. Lee; Yun-Ho Ahn (Chemical Engineering Journal, 2026)

Palaeochannels as hidden pathways of water flow in agricultural alluvial landscapes: A review of concepts and suggested future directions for modelling - Han She Lim; Alexander W. Cheesman; Paul N. Nelson; Rohan Eccles; Felix Egger; Marcus Bulstrode; Tony Weber (Journal of Hydrology, 2026)

Dopaminergic expression and the regulation of foraging in response to water stress - J. Frances Kamhi; Dajia Ye; Jason Chen; Han Lam Do; Corinne W. Marble; Jonathan Starcke; Ignacio Arganda-Carreras; Deborah M. Gordon (Journal of Insect Physiology, 2026)

Invasions of alien plants pose unprecedented challenges to China’s nature reserves under climate change - Jia-Xin Wang; Rainer W. Bussmann; Fei Qin; Yun-Fen Liang; Bao-Cai Han; Hai-Yan Bi; Tian-Tian Xue; Sheng-Xiang Yu (Biodiversity and Conservation, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

Two-year field testing of genetically engineered American chestnut reveals fungal blight tolerance - Thomas Klak; Steven E. Travis; Virginia Grace May; Ek Han Tan; Matthew W. H. Chatfield; Miranda Wheeler (New Forests, 2026)

Geothermal resource identification in Australia using shallow groundwater temperature data - Y. Han; L. T. White; W. G. P. Kumari; T. Murray (Australian Journal of Earth Sciences, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Low-pressure CO2 capture via semi-clathrate hydrates: Phase equilibria and structural analysis - Jae-Cheol Lee; Min-Kyung Kim; Ahhyun Roh; Haemin Seo; Jinmo Park; Jihye Lee; Yo-Han Kim; Jae W. Lee; Yun-Ho Ahn (Journal of Environmental Chemical Engineering, 2026)

The moon's formation time recorded in lunar mare basalts - Mu-Han Yang; Qian W.L. Zhang; Richard W. Carlson; Bi-Wen Wang; Dongjian Ouyang; Qiu-Li Li (Icarus, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Reducing the Discrepancy in Quantifying the Temperature Dependence of Global Wetland Methane Emission - Han Hu; Ke Xue; Yishen Sun; Qing Zhu; Hans K. Carlson; Ruiwen Hu; Rong‐Xi Tan; Chao Qian; Weigen Huang; Jizhong Zhou; Jingdong Mao; Thomas W. Crowther; et al. (Global Change Biology, 2026)
Understanding the apparent temperature dependence of wetland methane emissions ( E M ) is critical for predicting climate‐carbon feedbacks, yet current estimates remain constrained by observational limitations and methodological inconsistencies. The inherent biogeographic heterogeneity of wetland ecosystems combined with sparse, unevenly distributed flux measurements introduces substantial uncertainty in characterizing spatial patterns of E M . This knowledge gap impedes accurate projections of wetland methane contributions under climate warming scenarios. Here, we develop a framework that integrates mixed‐effects models with artificial intelligence techniques to resolve scale‐dependent patterns in methane emission thermodynamics across global wetlands. Our unified framework demonstrates that only 73.6% (5th–95th quantiles: 71.8%–75.4%) of the global wetland area conforms to classical Arrhenius‐type temperature dependence. This framework can predict 69.5% (67.9%–71.1%) of the global wetlands with high confidence using the Mahalanobis distance and area of applicability tests. We quantify the weighted mean E M across high‐confidence predictable areas of 0.694 eV, with latitudinal differentiation: tropical (0.634 eV), temperate (0.678 eV), and boreal (0.745 eV) wetlands exhibit progressively stronger temperature responses. Ignoring these biogeographic variations could result in underestimation of projected end‐century methane emissions by 4.2%–13.3% across selected socioeconomic pathway scenarios. Our study refined the temperature sensitivity parameter in coupled climate‐carbon cycle models, thereby enhancing predictive accuracy of future global warming trends and informing strategic responses to climate change mitigation.

Highly virulent Aerococcus viridans activates the RIPK3 signaling pathway, inducing necroptosis and inflammation in bovine mammary epithelial cells and murine mammary tissue - Siyu Meng; Maolin Xu; Xian Deng; Zimeng Zhu; Herman W. Barkema; John P. Kastelic; Eduardo R. Cobo; Bo Han; Gang Liu (Veterinary Microbiology, 2026)

PM2.5 exposure risks in urban outdoor jogging: multiple environmental determinants and mitigation strategies - L. Han; Y. J. Qi; L. Luo; W. Ding; K. Li; W. Li; L. Y. Tang (International Journal of Environmental Science and Technology, 2026)

The analysis of road stormwater runoff pollution in the typical coastal city of Lianyungang, East China - H. Leng; H. Luo; R. Han; W. Wu; B. Song; Y. Zhao; B.-J. He (International Journal of Environmental Science and Technology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A full sub-2 nm and acid-resistant MOF-COF ionic diode membrane for efficient ionic gradient power generation - Norman C.-R. Chen; Po-Chun Han; Li-Hsien Yeh; Yu-Hsiang Peng; Chia-An Lung; Yusuke Yamauchi; Kevin C.-W. Wu (Chemical Engineering Journal, 2025)

2.2-billion-year-old KREEP-rich volcanism on the Moon - Mu-Han Yang; Qian W.L. Zhang; Qiu-Li Li; Ross N. Mitchell; Richard W. Carlson; Zhu-Yin Chu; Yu Liu; Yi Chen; Shun Guo; Ding-Shuai Xue; Bin Su; Xu Tang; et al. (Science Bulletin, 2025)

Centennial-scale evolution, source apportionment, and ecological risks of heavy metals in Daya Bay, South China sea - Xiangtian Man; Jian Sun; Yu Xiang; Hong Su; Honghui Huang; Yangguang Gu; Han Zhang; Richard W. Jordan; Shijun Jiang (Environmental Pollution, 2025)

Halide anions-facilitated structural manipulation in Mn-based hybrids for multicolor emission and X-ray imaging - Tong Chang; Tongtong Kou; Qilin Wei; Liang Wang; Xiulian Cai; Huanxin Su; Yuanxiang You; Xin Li; Xinxin Han; Shiguo Han; William W. Yu (Chemical Engineering Journal, 2025)

Reconstructing historical catch trends of threatened sharks and rays based on fisher ecological knowledge - Guido Leurs; Rima W. Jabado; Assana Camará; Lilísio Dos Santos; Diosnes Manuel Nonque; Thije J. Zuidewind; Iça Barry; Pierre Campredon; Benja Blaschke; Karin de Boer; Nadia Hijner; Han Olff; et al. (Conservation Biology, 2025)
Small‐scale fisheries often lack historical shark and ray catch information, hampering their management. We reconstructed historical catch trends and current fishing pressure by combining local ecological knowledge, satellite‐based vessel counts, and a short‐term landing‐site survey. To test the effectiveness of this method, we focused on the Bijagós Archipelago (Guinea‐Bissau, West Africa), where historical fisheries data are lacking. Benthic rays (stingrays [Dasyatidae] and butterfly rays [ Gymnura spp.]), benthopelagic rays (duckbill eagle rays [ Aetomylaeus bovinus ] and cownose rays [ Rhinoptera marginata ]), guitarfish ( Glaucostegus and Rhinobatos spp.), requiem sharks (Carcharhinidae), and hammerhead sharks ( Sphyrna spp.) declined in abundance by 81.5–96.7% (species dependent) from 1960 to 2020. Fishing effort increased annually: fishing trip duration by 42.0% (SE 3.4), numbers of fishing vessels at sea as perceived by fishers by 36.3% (1.0) (1960–2020), and number of vessels by 12.0% (1.1) (2007–2022). We estimated that in 2020, fishing vessels collectively captured 61–264 sharks and 522–2194 rays per day in the archipelago, depending on the proportion of the fishing fleet that was active (i.e., low fleet activity of 18% and high fleet activity of 80%). We advocate for reducing shark and ray catches by regulating fleet size, reinforcing boundaries of protected areas, and collecting fisher‐dependent information on shark and ray landings to safeguard these vulnerable species and coastal livelihoods. We demonstrated the effectiveness of using this 3‐pronged approach to provide baseline data on shark fisheries, a common challenge in areas with small‐scale fisheries and limited research capacity.

Surfactant-assisted colloidal size and charge control in perovskite solutions for high-performance and stable solar cells - Gyeong G. Jeon; Sang Eun Yoon; Jonghoon Han; Hye W. Chun; So Jeong Shin; Min Jun Choi; Sang Uk Park; Seo-Jin Ko; Shujuan Huang; Nochang Park; Jong H. Kim; Jincheol Kim (Chemical Engineering Journal, 2025)

Integrated membrane contactor system using NaOH solution for biogas purification and polyhydroxyalkanoate synthesis via cyanobacteria - Abduljelil W. Sabir; Dong Yun Han; Se Wan Kim; Simon MoonGeun Jung; Ga-Hyeon Kim; Karl Forchhammer; Jong-Hee Kwon; Pyung Soo Lee (Chemical Engineering Journal, 2025)

Calcium hydroxide dissolution rates: Dependence on temperature and saturation - Yoonjung Han; Mine G. Ucak-Astarlioglu; Jedadiah F. Burroughs; Jeffrey W. Bullard (Chemical Engineering Journal, 2025)

Impact of indigenous vs. cultivated microalgae strains on biomass accumulation, microbial community composition, and nutrient removal in algae-based dairy wastewater treatment - KhinKhin Phyu; Suli Zhi; David W. Graham; Yuang Cao; Xiaoyu Xu; Jiahua Liu; Han Wang; Keqiang Zhang (Bioresource Technology, 2025)

Synthesis of Population Trends Reveals Seascape‐Wide Reorganisation of Biodiversity From Microalgae to Birds - Anika Happe; Kasper J. Meijer; Jan‐Claas Dajka; Oscar Franken; Holger Haslob; Laura L. Govers; Michael Kleyer; Annebelle C. M. Kok; Lucie Kuczynski; Kertu Lõhmus; Sancia E. T. van der Meij; Han Olff; et al. (Global Change Biology, 2025)
Many monitoring programs aim to understand regional biodiversity patterns in relation to global and regional conservation targets, using either community‐wide biodiversity metrics to describe the community status or trends of pre‐selected “key” species as biodiversity change indicators. However, the former often lacks information on which species are changing, and the latter is heavily skewed towards specific taxa, potentially overlooking changes in other, functionally important taxa. We gathered an extensive set of monitoring data with over 3000 population trends (ranging from 5 to 91 years in duration) for a wide range of taxa across the Wadden Sea. We combined a systematic and quantitative categorization of population trends (weighted vote count) with a meta‐analysis on different taxonomic levels. This allowed the first cross‐taxa synopsis of species declines and increases and determined their directionalities throughout time. Our meta‐analysis showed an overall decrease in population size for fish, zooplankton, and plant species, while birds showed an overall increase. However, these increases mask recent negative trends within specific bird groups since the late 1990s. In contrast, fish populations exhibited declines over the entire monitoring period. Species with declining populations (losers) were phylogenetically related, whereas species with increasing populations (winners) represented various organismal groups. Directionality and onsets of change in population trends were temporally synchronized throughout several groups, such as bivalves, fish, and birds, and may provide warning signals for future local extinctions in these taxa. Our analysis moves beyond typical indicator species by including the entire species inventory of the system. Basal trophic levels of aquatic ecosystems, such as zooplankton and phytoplankton, are often missing from policy assessments but are among the most important organism groups for ecosystem functioning. Here, we show that without additional monitoring effort, a systematic analysis of population trends adds to our understanding of trophic and compositional restructuring of ecosystems.

Contrasting responses of flowering phenology in C 3 and C 4 plants shape grassland community structure under global change - Lu Bai; Guodong Han; Lin Jiang; Thomas W. Crowther; Constantin M. Zohner; Kailiang Yu; Zhuwen Xu; Zhongwu Wang; Qian Wu; Yi Zhu; Jinglei Tang; Haiyan Ren (Ecology, 2025)
Climate change is known to affect plant phenology. Yet, the sensitivity of flowering phenology in dryland regions to climate change, and the potential implications for community composition, remain largely unexplored. Here, we used an 18‐year field experiment to investigate the effects of climate warming and nitrogen addition on flowering phenology of four C 3 plant species and two C 4 plant species, and the cascading effects on the relative abundance of C 3 and C 4 plants in a desert steppe. Across the past 10 years of the experiment (2013–2022), we found that warming had a greater effect on phenological shifts in C 3 than in C 4 plants. Warming significantly advanced the flowering time of C 3 plants by 4.3 ± 0.1 days and of C 4 plants by 2.8 ± 0.1 days, respectively. Warming also reduced the duration of flowering by 1.8 ± 0.1 days for C 3 plants but had no effect on C 4 plants, and decreased the dominance of C 3 plants compared to C 4 plants. Nitrogen addition extended the duration of flowering of C 4 plants by 3.4 ± 0.2 days and increased their relative dominance, while decreasing the dominance of C 3 plants. Structural equation models revealed that these phenological responses were largely driven by soil temperature and soil water availability. Our results demonstrate that the different phenological responses of C 3 and C 4 plants contribute to shifts in dominance between these plant types in temperate dryland ecosystems under global changes.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Multiple Nutrient Additions Homogenize Multidimensional Plant Stoichiometry in a Meadow Steppe - Yang Peng; Jian‐Xia Yang; Eric W. Seabloom; Jordi Sardans; Josep Peñuelas; Hai‐Yang Zhang; Cun‐Zheng Wei; Xing‐Guo Han (Global Change Biology, 2025)
Human activities are altering terrestrial ecosystem biogeochemistry globally by augmenting the availability of multiple biologically essential nutrients, thereby potentially altering plant internal concentrations (i.e., stoichiometry) across a diverse array of elements. These shifts in plant nutrient concentrations may subsequently impact crucial ecosystem processes, including litter decomposition, herbivory by insects and large animals, and ecosystem productivity. However, most work on the alteration of plant stoichiometry has focused on a few macronutrients (e.g., nitrogen or phosphorus), despite the potential importance of many other elements. In this study, we conducted a comprehensive field experiment in the Inner Mongolia Steppe, manipulating eight distinct nutrients to examine their effects on both soil and plant tissue concentrations. Our findings reveal that adding most nutrients increased their corresponding available contents in the soil. In most cases, the addition of nutrients also increased their corresponding concentrations in plant tissues at both species and community levels. Besides, multiple nutrient additions had greater effects on soil available nutrient contents than on plant internal nutrient concentrations. Notably, the concurrent addition of multiple nutrients led to a significant homogenization of plant stoichiometry among different species within the same community. This homogenization might influence interspecific interactions and coexistence within grassland ecosystems. Our findings advanced our comprehension of how anthropogenic nutrient enrichment may simplify plant nutrient profiles, thereby influencing grassland biodiversity and ecosystem functionality.

Rodent Diets Incorporated with Live Biotherapeutic Products (LBPs): An Innovative Dosing Strategy to Support Preclinical Animal Studies on LBP Intervention - Haixi Cui; Yongrong Zhang; Hua Yu; R. Gary Hollenbeck; Lydia Nyasae; Yihan Wang; Yiguang Han; Zhiyong Yang; Hanping Feng; Stephen W. Hoag (AAPS PharmSciTech, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Iron oxides promote physicochemical stabilization of carbon despite enhancing microbial activity in the rice rhizosphere - Han Sun; Xiaomin Ma; Lukas Van Zwieten; Yu Luo; Robert W. Brown; Georg Guggenberger; Sheng Tang; Yakov Kuzyakov; Peduruhewa H. Jeewani (Science of The Total Environment, 2025)

Nutrient effects on plant diversity loss arise from nutrient identity and decreasing niche dimension - Yang Peng; Jianxia Yang; Eric W. Seabloom; Andrew R. Leitch; Ilia J. Leitch; Ruzhen Wang; Cunzheng Wei; Xingguo Han (Ecology, 2025)
Two hypotheses have been used to explain the loss of plant diversity with nutrient addition. The nutrient identity hypothesis posits that biodiversity loss is due to a specific limiting nutrient, such as nitrogen (N) or phosphorus (P), while the niche dimension hypothesis posits that adding a larger number of limiting nutrients, regardless of their identity, results in biodiversity loss. These two hypotheses have not previously been tested together simultaneously. Here, we conduct that analysis to enable their relative effect sizes to be compared. We manipulated the supply of eight nutrients in the same experimental meadow grassland site to isolate the effects of the identity of added nutrients versus the number of added nutrients on biodiversity loss. We found support for both hypotheses, with the largest negative effects on biodiversity measures being due to N, or N and P treatment, with additional more minor effects of the number of added nutrients. Structural equation models (SEMs) suggested both identity and number of added nutrients had direct negative effects on biodiversity, likely caused by species' innate ability to competitively respond to nutrients, especially in response to disease, herbivory, and stress. SEMs also suggested indirect effects arising from nutrient‐driven increases in aboveground biomass, which resulted in intensified competition for light and the competitive exclusion of short‐statured species. These effects were exacerbated by the nutrients N and P which caused a shift in biomass accumulation from belowground to aboveground. The results highlight that a multi‐nutrient perspective will improve our ability to effectively manage, monitor, and restore ecosystems.

Improving hydrological modeling to close the gap between elevated CO2 concentration and crop response: Implications for water resources - Na Wen; Yiwen Han; Junyu Qi; Gary W. Marek; Danfeng Sun; Puyu Feng; Raghavan Srinivasan; De Li Liu; Yong Chen (Water Research, 2024)

Effects of saccharide type and extended heating on the Maillard reaction and physicochemical properties of high-solid gelatin gels - Ruican Wang; Xinyu Zhai; Richard W. Hartel; Yawei Chang; Wenwen Pang; Wen Han; Huan Lv; Shuo Wang (Food Chemistry, 2024)

A covalently bonded, LiF-rich solid electrolyte interphase for Li metal batteries with superior low-temperature performance - Shuiyin Chen; Xiaodong Meng; Dengji Han; Shang Chen; Ji Zhou; Manyun Wang; Jiamin Wang; Zhongli Wang; Christopher W. Bielawski; Jianxin Geng (Chemical Engineering Journal, 2024)

FireBox and CharBoss: An alternative to open burning of woody biomass - Paul O. Oyier; Han-Sup Han; Dipita Ghosh; Nathaniel Anderson; Deborah S. Page-Dumroese; Daniel W. McCollum; Joanne M. Tirocke; Derek N. Pierson (Biomass and Bioenergy, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

β-adrenergic stimulation after rewarming does not mitigate hypothermia-induced contractile dysfunction in rat cardiomyocytes - Torstein Schanche; Young Soo Han; Cole W. Jensen; Grace M. Arteaga; Torkjel Tveita; Gary C. Sieck (Cryobiology, 2024)

Cryopreservation-enhanced differentiation capacity of embryogenic cultures of Castanea mollissima - Shuangxian Liu; Liang Lin; Biao Han; Junchao Ma; Hugh W. Pritchard; Xiaojian Hu; Min Deng; Hongying Chen (Cryobiology, 2024)

Using stable isotopes to inform water resource management in forested and agricultural ecosystems - Francesca Scandellari; Taha Attou; Adrià Barbeta; Fabian Bernhard; Concetta D’Amato; Katya Dimitrova-Petrova; Amanda Donaldson; Oludare Durodola; Stefano Ferraris; Marius G. Floriancic; Gabriela Fontenla-Razzetto; Malkin Gerchow; et al. (Journal of Environmental Management, 2024)

Temporal changes in the fermentation characteristics, bacterial community structure and the functionality of the predicted metagenome of a batch fermenter medium containing the upper gastrointestinal enzyme resistant fraction of white sorghum (Sorghum bicolor L. Moench) - Samanthi W. Pelpolage; Haruhi Kobayashi; Naoki Fukuma; Michiyo Hoshizawa; Tetsuo Hamamoto; Kyu-Ho Han; Michihiro Fukushima (Food Chemistry, 2024)

IC100, a humanized therapeutic monoclonal anti-ASC antibody alleviates oxygen-induced retinopathy in mice - Huijun Yuan; Shaoyi Chen; Matthew R. Duncan; Juan Pablo de Rivero Vaccari; Robert W. Keane; W. Dalton Dietrich; Tsung-Han Chou; Merline Benny; Augusto F. Schmidt; Karen Young; Kevin K. Park; Vittorio Porciatti; et al. (Angiogenesis, 2024)
Background Retinopathy of prematurity (ROP), which often presents with bronchopulmonary dysplasia (BPD), is among the most common morbidities affecting extremely premature infants and is a leading cause of severe vision impairment in children worldwide. Activations of the inflammasome cascade and microglia have been implicated in playing a role in the development of both ROP and BPD. Apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) is pivotal in inflammasome assembly. Utilizing mouse models of both oxygen-induced retinopathy (OIR) and BPD, this study was designed to test the hypothesis that hyperoxia induces ASC speck formation, which leads to microglial activation and retinopathy, and that inhibition of ASC speck formation by a humanized monoclonal antibody, IC100, directed against ASC, will ameliorate microglial activation and abnormal retinal vascular formation. Methods We first tested ASC speck formation in the retina of ASC-citrine reporter mice expressing ASC fusion protein with a C-terminal citrine (fluorescent GFP isoform) using a BPD model that causes both lung and eye injury by exposing newborn mice to room air (RA) or 85% O 2 from postnatal day (P) 1 to P14. The retinas were dissected on P14 and retinal flat mounts were used to detect vascular endothelium with AF-594-conjugated isolectin B4 (IB4) and citrine-tagged ASC specks. To assess the effects of IC100 on an OIR model, newborn ASC citrine reporter mice and wildtype mice (C57BL/6 J) were exposed to RA from P1 to P6, then 75% O 2 from P7 to P11, and then to RA from P12 to P18. At P12 mice were randomized to the following groups: RA with placebo PBS (RA-PBS), O 2 with PBS (O 2 -PBS), O 2 + IC100 intravitreal injection (O 2 -IC100-IVT), and O 2 + IC100 intraperitoneal injection (O 2 -IC100-IP). Retinal vascularization was evaluated by flat mount staining with IB4. Microglial activation was detected by immunofluorescence staining for allograft inflammatory factor 1 (AIF-1) and CD206. Retinal structure was analyzed on H&E-stained sections, and function was analyzed by pattern electroretinography (PERG). RNA-sequencing (RNA-seq) of the retinas was performed to determine the transcriptional effects of IC100 treatment in OIR. Results ASC specks were significantly increased in the retinas by hyperoxia exposure and colocalized with the abnormal vasculature in both BPD and OIR models, and this was associated with increased microglial activation. Treatment with IC100-IVT or IC100-IP significantly reduced vaso-obliteration and intravitreal neovascularization. IC100-IVT treatment also reduced retinal microglial activation, restored retinal structure, and improved retinal function. RNA-seq showed that IC100 treatment corrected the induction of genes associated with angiogenesis, leukocyte migration, and VEGF signaling caused by O 2 . IC100 also corrected the suppression of genes associated with cell junction assembly, neuron projection, and neuron recognition caused by O 2 . Conclusion These data demonstrate the crucial role of ASC in the pathogenesis of OIR and the efficacy of a humanized therapeutic anti-ASC antibody in treating OIR mice. Thus, this anti-ASC antibody may potentially be considered in diseases associated with oxygen stresses and retinopathy, such as ROP.

Biological and genomic characterization of 4 novel bacteriophages isolated from sewage or the environment using non-aureus Staphylococci strains - Xiaoping Li; Baoling Zhang; Xiaofang Tong; Tao Zhou; Moli Li; Herman W. Barkema; Diego B. Nobrega; John P. Kastelic; Chuang Xu; Bo Han; Jian Gao (Veterinary Microbiology, 2024)

Quantitative Applications of Weather Satellite Data for Nowcasting: Progress and Challenges - Jun Li; Jing Zheng; Bo Li; Min Min; Yanan Liu; Chian-Yi Liu; Zhenglong Li; W. Paul Menzel; Timothy J. Schmit; John L. Cintineo; Scott Lindstrom; Scott Bachmeier; et al. (Journal of Meteorological Research, 2024)

Change in rate of healthcare encounters for respiratory infection from air pollution exposure after improved vehicle emissions standards in New York State - Daniel P. Croft; Mark J. Utell; Han Liu; Shao Lin; Philip K. Hopke; Sally W. Thurston; Yunle Chen; David Q. Rich (Air Quality, Atmosphere & Health, 2024)
The introduction of Tier 3 light-duty vehicles with reduced emissions began in New York State (NYS) in 2017, with required compliance by 2025. We hypothesized that improved air quality during the early implementation of Tier 3 (2017–2019) would result in reduced rates of hospitalizations and emergency department (ED) visits for respiratory infection associated with increased PM 2.5 compared to 2014–2016 (pre-Tier 3). Using data on adult patients hospitalized or having an ED visit for influenza, upper respiratory infection, culture-negative pneumonia, or respiratory bacterial infection, living within 15 miles of six air quality monitoring sites in NY, and a case-crossover design and conditional logistic regression, we estimated the rates of respiratory infection hospitalizations and ED visits associated with increased ambient PM 2.5 concentrations in the previous 0–6 days and each week thereafter up to 1 month. Interquartile range (IQR) increases in PM 2.5 in the previous 6 days were associated with 4.6% (95% CI: − 0.5, 10.1) and 11.9% (95% CI = 6.1, 18.0) increased rates of influenza hospitalizations in 2014–2016 and 2017–2019, respectively. This pattern of larger relative rates in 2017–2019 observed at all lag times was only present in males hospitalized for influenza but not other infections or in females. The rates of respiratory infection visits associated with increased PM 2.5 were generally not reduced in this early Tier 3 implementation period compared to 2014–2016. Limited fleet penetration of Tier 3 vehicles and differences in particle deposition, infection type, and sex by period may all have contributed to this lack of improvement.

Host specificity of plant‐associated bacteria is negatively associated with genome size and host abundance along a latitudinal gradient - Zihui Wang; Geneviève Lajoie; Yuan Jiang; Minhua Zhang; Chengjin Chu; Yongfa Chen; Shuai Fang; Guangze Jin; Mingxi Jiang; Juyu Lian; Yanpeng Li; Yu Liu; et al. (Ecology Letters, 2024)
Host specialization plays a critical role in the ecology and evolution of plant–microbe symbiosis. Theory predicts that host specialization is associated with microbial genome streamlining and is influenced by the abundance of host species, both of which can vary across latitudes, leading to a latitudinal gradient in host specificity. Here, we quantified the host specificity and composition of plant–bacteria symbioses on leaves across 329 tree species spanning a latitudinal gradient. Our analysis revealed a predominance of host‐specialized leaf bacteria. The degree of host specificity was negatively correlated with bacterial genome size and the local abundance of host plants. Additionally, we found an increased host specificity at lower latitudes, aligning with the high prevalence of small bacterial genomes and rare host species in the tropics. These findings underscore the importance of genome streamlining and host abundance in the evolution of host specificity in plant‐associated bacteria along the latitudinal gradient.

Comprehensive cannabinoid profiling of acid-treated CBD samples and Δ8-THC-infused edibles - Si Huang; Teris A. van Beek; Frank W. Claassen; Hans-Gerd Janssen; Ming Ma; Bo Chen; Han Zuilhof; G.IJ. Salentijn (Food Chemistry, 2024)

Mutual facilitation between foundation species Mytilus edulis and Lanice conchilega promotes habitat heterogeneity on tidal flats - Janne Nauta; Kasper J. Meijer; Lissie W. de Groot; Valérie C. Reijers; Tjeerd J. Bouma; Daphne van der Wal; Han Olff; Sander J. Holthuijsen; Allert I. Bijleveld; Henk W. van der Veer; Oscar Franken; Laura L. Govers (Frontiers in Marine Science, 2024)
Foundation species that modify their habitat can facilitate other species, including other foundation species. Most studies focus solely on a single foundation species, overlooking such facilitation cascades. In this study, we investigated the interactions between the two coastal foundation species Mytilus edulis (blue mussel) and Lanice conchilega (sand mason worm). We investigated whether these species engage in facilitative interactions or if their association simply reflects a shared ecological niche on the soft-sediment intertidal flats of the Dutch Wadden Sea. To do so, we performed species distribution modeling, manipulative field experiments, and field surveys. We found a positive association between both foundation species, with a 2.45 times higher occurrence of both species compared to a random distribution. In addition, these species partially occupied the same ecological niche. We demonstrated that L. conchilega provided settlement substrate for M. edulis spat, increasing densities by 400 times compared to bare plots. Furthermore, M. edulis reefs facilitated L. conchilega occurrence in the wake of the reef. Biogenic reef development revealed that this interspecific facilitation resulted in spatial habitat heterogeneity. Therefore, we conclude that interspecific facilitation can significantly enhance the occurrence of these two important intertidal foundation species. Acknowledgment of such complex facilitation interactions has an untapped potential for improving the success of restoration and conservation programs.

Evaluating the future total water storage change and hydrological drought under climate change over lake basins, East Africa - Ayalkibet M. Seka; Huadong Guo; Jiahua Zhang; Jiaqi Han; Eyale Bayable; Gebiaw T. Ayele; Habtamu T. Workneh; Olfa T. Bayouli; Fabien Muhirwa; Kidane W. Reda (Journal of Cleaner Production, 2024)

High stocking rates effects in continuous season long grazing reduces the contribution of microbial necromass to soil organic carbon in a semi-arid grassland in Inner Mongolia - Tianqi Zhao; Rongzhen Suo; Aklilu W. Alemu; Shaoyu Li; Jiahua Zheng; Naijing Lu; Feng Zhang; Jirong Qiao; Jianying Guo; Alan D. Iwaasa; Guodong Han; Mengli Zhao; et al. (Journal of Environmental Management, 2024)

The relationship of cancer history and chronic disease status to colorectal cancer screening: A cross-sectional analysis of 2020–2021 Behavioral Risk Factor Surveillance System - Meng-Han Tsai; Alice W. Lee; Minjee Lee (Cancer Causes & Control, 2024)

Hydrogen separation from hydrogen-compressed natural gas blends through successive hydrate formations - Geumbi Han; Wonhyeong Lee; Min-Kyung Kim; Jae W. Lee; Yun-Ho Ahn (Chemical Engineering Journal, 2024)

The impact of marital status on tumor aggressiveness, treatment, and screening among black and white men diagnosed with prostate cancer - Saira Khan; Lindsay Fuzzell; Marvin Langston; Yunan Han; Justin X. Moore; Keon Gilbert; Siobhan Sutcliffe; Jeannette T. Bensen; James L. Mohler; Elizabeth T.H. Fontham; Lixin Song; Marquita W. Lewis-Thames (Cancer Causes & Control, 2024)

An analysis of lncRNAs related to fiber quality and the discovery of their target genes in a Gossypium hirsutum line with Gossypium mustelinum introgression - Baohua Wang; Meijun Ji; Hui Fang; Haijing Gu; Teame Gereziher Mehari; Jinlei Han; Wenxiang Feng; Xuehan Huo; Jingxia Zhang; Yu Chen; Jun Zhang; Allah Ditta; et al. (Theoretical and Applied Genetics, 2024)

Fluorescence lifetime imaging microscopy as a tool to characterize spice powder variations for quality and authenticity purposes: A ginger case study - Qing Han; Sara W. Erasmus; Arjen Bader; Christos Fryganas; Christopher T. Elliott; Saskia M. van Ruth (Food Research International, 2024)

Multivariate investigation of aging in mouse models expressing the Alzheimer’s protective APOE2 allele: integrating cognitive metrics, brain imaging, and blood transcriptomics - Hae Sol Moon; Ali Mahzarnia; Jacques Stout; Robert J. Anderson; Madison Strain; Jessica T. Tremblay; Zay Yar Han; Andrei Niculescu; Anna MacFarlane; Jasmine King; Allison Ashley-Koch; Darin Clark; et al. (Brain Structure and Function, 2023)

P26-12: Acute and subacute toxicity profiles in Sprague-Dawley (SD) rats treated with Piperis Longi Fructus (PLF) aqueous extract - Y.-B. Kim; W.-J. Im; K.-H. Han (Toxicology Letters, 2023)

P26-11: Acute and subacute toxicity profiles in Sprague-Dawley (SD) rats treated with Piperis Longi Fructus (PLF) Powder - K.-H. Han; W.-J. Im; Y.-B. Kim (Toxicology Letters, 2023)

P24-13: Round Robin Study in Korea on alternative test method for evaluating skin irritation potential of medical devices - J. Yi; Y.S. Park; J.E. Im; H.-W. Moon; J.H. Kim; K.J. Kim; H.S. Yoon; Y. Lee; H.J. Ko; I.S. Kim; J.S. Kim; J.-S. Han; et al. (Toxicology Letters, 2023)

P19-07: 13-week repeated-dose oral toxicity study in rats treated with a mixture of Cirsium japonicum and Brassica oleracea extracts - W.-J. Im; M.-H. Yang; H. Park; J.-S. Han; J.-W. Cho; M.H. Yoo; Y.-B. Kim (Toxicology Letters, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Bridging the gap between artificial intelligence and mental health - Tangsheng Lu; Xiaoxing Liu; Jie Sun; Yanping Bao; Björn W. Schuller; Ying Han; Lin Lu (Science Bulletin, 2023)

Increase of carbon storage in the Qinghai-Tibet Plateau: Perspective from land-use change under global warming - Miaoni Gao; Runhong Xu; Jinlong Huang; Buda Su; Shan Jiang; Peijun Shi; Haifeng Yang; Yun Xing; Dongfang Wang; Han Jiang; Zbigniew W. Kundzewicz; Tong Jiang (Journal of Cleaner Production, 2023)

Interpreting the variation in particle size of ground spice by high-resolution visual and spectral imaging: A ginger case study - Qing Han; Joseph Peller; Sara W. Erasmus; Christopher T. Elliott; Saskia M. van Ruth (Food Research International, 2023)

Corrigendum to “Carbon capture by macroalgae Sarcodia suae using aquaculture wastewater and solar energy for cooling in subtropical regions” [Sci. Total Environ. 855 (2023) 158850] - W. Sanjaya Weerakkody; Ka Hin Ling; Hsueh-Han Hsieh; Vicente G. Abedneko; Jeng-Feng Shyu; Tse-Min Lee; Yung-Yen Shih; R.R.M.K.P. Ranatunga; Peter H. Santschi; Chin-Chang Hung (Science of The Total Environment, 2023)

In-drain denitrifying woodchip bioreactors for reducing nitrogen runoff from sugarcane - Alexander W. Cheesman; Shannon Todd; Liz Owen; Dennis AhKee; Han She Lim; Maureen Masson; Paul N. Nelson (Ecological Engineering, 2023)

Rebound effect of carbon emissions of new energy vehicle consumption: a case study of Beijing - J. Zhou; W. Fang; X. Han; Q. Sun; D. Liu; S. Liu (International Journal of Environmental Science and Technology, 2023)

Study on the Vibration Characteristics of Marine Riser Based on Flume Experiment and Numerical Simulation - Qiurui Cai; Zhengnong Li; Ricky W. K. Chan; Han Luo; Guodi Duan; Bin Huang; Honghua Wu (Journal of Marine Science and Engineering, 2023)
This study investigated vortex-induced vibrations of marine risers in Ocean Thermal Energy Conversion systems. Flume experiments were conducted under two conditions: Condition 1 was with a fixed riser bottom, and Condition 2 was with a fixed bottom on a mooring platform. The cross-flow acceleration of the riser was measured at different current velocities, and corresponding vibration responses were analyzed. Numerical simulations based on the flume experiments were employed to validate the reliability of the simulation method. Results from the flume experiments revealed vortex-induced resonance in Condition 1 when the flow velocity approached the riser’s natural frequency. In Condition 2, similar vibration responses were observed, with maximum acceleration occurring during flow velocity-induced vortex-induced vibrations. However, at higher flow velocities, the acceleration response showed a decrease followed by an increase, indicating the excitation of higher-order modes. The numerical simulations matched the flume experiments in Condition 1. In Condition 2, while the acceleration response and frequency agreed during vortex-induced resonance, discrepancies arose in the flow velocity that caused vortex-induced vibrations compared to the flume experiments. This study demonstrated the accuracy of numerical simulations in reflecting vortex-induced vibrations of risers, providing a foundation for further research on complex riser systems.

Late paleozoic–mesozoic subduction and accretion of the paleo-pacific plate: insights from the ocean plate stratigraphy of the wandashan accretionary complex, NE China - Yong Liang; Han Zheng; Huan Li; Michael W. Förster; Zhihan Li (International Geology Review, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

Carbon capture by macroalgae Sarcodia suae using aquaculture wastewater and solar energy for cooling in subtropical regions - W. Sanjaya Weerakkody; Ka Hin Ling; Hsueh-Han Hsieh; Vicente G. Abedneko; Jeng-Feng Shyu; Tse-Min Lee; Yung-Yen Shih; R.R.M.K.P. Ranatunga; Peter H. Santschi; Chin-Chang Hung (Science of The Total Environment, 2023)

Higher blood selenium level is associated with lower risk of hyperhomocysteinemia in the elderly - Ting Wang; Liqin Su; Xi Chen; Sisi Wang; Xu Han; Yibin Cheng; Shaobin Lin; Liang Ding; Jingyi Liu; Chen Chen; Frederick W. Unverzagt; Ann M. Hake; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

Probing the nature of soil organic matter - Zhe (Han) Weng; Johannes Lehmann; Lukas Van Zwieten; Stephen Joseph; Braulio S. Archanjo; Bruce Cowie; Lars Thomsen; Mark J. Tobin; Jitraporn Vongsvivut; Annaleise Klein; Casey L. Doolette; Helen Hou; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Characterization and thermal removal of organophosphorus pesticides in soils from a former agrochemical factory - W. Han; Y. Ye; S. Liu; J. Sima (International Journal of Environmental Science and Technology, 2022)

Pseudoephedrine hydrochloride causes hyperactivity in zebrafish via modulation of the serotonin pathway - Yini Zhou; Tonglaga Li; Shangzi Zhou; Han Xu; Xiaoyu Yin; Hao Chen; Xuan Ni; Meirong Bai; Wuliji Ao; Jingfeng Yang; R. G. Ahmed; Xuefu Zhang; et al. (Metabolic Brain Disease, 2022)

Spray-Dried and Spray-Freeze-Dried Powder Formulations of an Anti-Interleukin-4Rα Antibody for Pulmonary Delivery - Harry W. Pan; Han Cong Seow; Jason C. K. Lo; Jinlin Guo; Lingqiao Zhu; Susan W. S. Leung; Chenghai Zhang; Jenny K. W. Lam (Pharmaceutical Research, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Species and Functional Dynamics of the Demersal Fish Community and Responses to Disturbances in the Pearl River Estuary - Zeyu Zeng; William W. L. Cheung; Han Lai; Huadong Yi; Sheng Bi; Haiyang Li; Xiaoli Chen; Yuqin Su; Xuange Liu; Qiuxian Chen; Zhilun Zhang; Xuchong Wei; et al. (Frontiers in Marine Science, 2022)
Fishery resources are threatened by environmental changes and anthropogenic pressures, particularly in coastal ecosystems. It is crucial to understand the changes of fish communities and their responses to environmental changes and human disturbances to formulate rational fisheries and ecosystem-based management. The Pearl River Estuary (PRE) is a typical sub-tropic coastal ecosystem located in the center of the Guangdong-Hong Kong-Macao Greater Bay Area in the northern South China Sea. The demersal fish in the PRE is traditionally targeted as commercial fishing and severely impacted by overexploitation and hypoxia in the last few decades. In this study, we analyze the fish survey data during the period of 2020~2021 using multivariate statistics to investigate the impacts of human disturbances on the species and functional dynamics of the demersal fish community in the PRE. The results reveal that dissolved oxygen and temperature have significant correlations with the functional traits of the demersal fish community. The impacts of hypoxia on the demersal fish vary with species and locations. We found that the mean functional redundancy of the demersal fish community in the PRE was high across three surveys, but the functional diversity was low in this region. The abundance and richness of the demersal fish community increased during the summer fishing moratorium in the South China Sea in 2021, but the functional diversity did not increase significantly. We conclude that the high functional redundancy in the PRE might not be sufficient to buffer against environmental disturbances because of its low functional diversity. Our study highlights the complicated interactions between the demersal fish community and disturbances in the PRE. Understanding the traits structure and functional diversity of the fish community can help elucidate the factors determining the dynamic responses of the fish community to disturbances.

Mechanical properties and fracture evolution process of Beishan granite under tensile state - C. S. Wang; J. F. Liu; Y. W. Zhao; S. J. Han (Bulletin of Engineering Geology and the Environment, 2022)

Truncation of the N-terminus of cardiac troponin I initiates adaptive remodeling of the myocardial proteosome via phosphorylation of mechano-sensitive signaling pathways - Chad M. Warren; Monika Halas; Paul H. Goldspink; Han-Zhong Feng; Anthony W. Herren; Beata M. Wolska; Pieter P. de Tombe; Jian-Ping Jin; R. John Solaro (Molecular and Cellular Biochemistry, 2022)

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Trametes suaveolens-derived biochar loaded on nanoscale zero-valent iron particles for the adsorption and reduction of Cr(VI) - W.-D. Wang; H.-T. Ma; W. Lin; P. Sun; L.-K. Zhang; J.-H. Han (International Journal of Environmental Science and Technology, 2022)

An analysis of coupling coordination relationship between regional economy and transportation: empirical evidence from China - Qiang Du; Xinqi Wang; Yi Li; Patrick X. W. Zou; Xiao Han; Meng Meng (Environmental Science and Pollution Research, 2022)

Target lines for recombinase-mediated gene stacking in soybean - Li Jiang; Ruyu Li; Zhiguo Han; Xiaohui Zhao; Dong Cao; David W. Ow (Theoretical and Applied Genetics, 2022)

Biodiversity alleviates the decrease of grassland multifunctionality under grazing disturbance: A global meta‐analysis - Ruiyang Zhang; Dashuan Tian; Han Y. H. Chen; Eric W. Seabloom; Guodong Han; Shaopeng Wang; Guirui Yu; Zhaolei Li; Shuli Niu (Global Ecology and Biogeography, 2022)
Aim Biodiversity drives the delivery of multiple ecosystem functions related to carbon and nutrient cycling (ecosystem multifunctionality, EMF), and biodiversity and ecosystem functioning are strongly threatened by intensive grazing in grasslands. However, it remains unclear how biodiversity regulates EMF changes in response to intensive grazing. Location Global. Time period From 1992 to 2018. Major taxa studied Grassland. Methods Here, we conducted a global synthesis using 373 paired observations from 90 published studies to address the responses of plant diversity, EMF and their relationships to grazing disturbance depending on grazing intensity, livestock type, grazing duration, and climatic aridity. Results Our results showed that EMF significantly decreased with increasing grazing intensity, but the negative EMF response was alleviated at high levels of plant diversity. The grazing‐induced changes in EMF increased linearly with the changes in plant diversity, with the slopes increasing by 78.9% from light to heavy grazing. In addition, the grazing‐induced decrease of EMF was stronger with longer grazing duration and more arid climates. Structural equation models suggested that grazing intensity reduced EMF largely via decreasing plant diversity, whereas upsizing livestock type promoted EMF by increasing plant diversity. Main conclusions This study highlights the key role of biodiversity in mediating EMF in response to intensifying grazing disturbance. We call for conservation of biodiversity to maintain grassland multifunctionality and services.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

The second wave of earthworm invasions in North America: biology, environmental impacts, management and control of invasive jumping worms - Chih-Han Chang; Marie L. C. Bartz; George Brown; Mac A. Callaham; Erin K. Cameron; Andrea Dávalos; Annise Dobson; Josef H. Görres; Bradley M. Herrick; Hiroshi Ikeda; Samuel W. James; Marie R. Johnston; et al. (Biological Invasions, 2021)

Eutrophication and Hypoxia in Tropical Negombo Lagoon, Sri Lanka - Hsueh-Han Hsieh; Ming-Hsiu Chuang; Yung-Yen Shih; W. Sanjaya Weerakkody; Wei-Jen Huang; Chin-Chang Hung; François L. L. Muller; R. R. M. K. P. Ranatunga; D. S. Wijethunga (Frontiers in Marine Science, 2021)
Hypoxic events are becoming frequent in some estuaries and coastal waters due to over-enrichment of anthropogenic nutrients, organic matter, and/or due to restricted water circulation. The coastal lagoons and estuaries of Sri Lanka are facing high population pressure and lacking sufficient infrastructure. Coastal lagoons may receive high anthropogenic inputs of natural or untreated nitrogen and phosphorus wastes, and consequently result in hypoxic conditions while sluggish circulation occurred. In this study, we examined the spatiotemporal variability of eutrophication and hypoxia in the Negombo Lagoon, one of the most productive and sensitive coastal ecosystems in Sri Lanka. Based on seasonal measurements of dissolved oxygen, nutrients, chlorophyll- a (Chl- a ), particulate and dissolved organic carbon (POC and DOC), we concluded that eutrophication and hypoxia occurred in both the dry and wet seasons. The main contributing factors were high seawater temperature and poor water circulation in the dry season and high nutrient loading combined with elevated POC and DOC inputs in the wet season.

Synthesis of a novel ZnFe2O4/porous biochar magnetic composite for Th(IV) adsorption in aqueous solutions - W. D. Wang; Y. X. Cui; L. K. Zhang; Y. M. Li; P. Sun; J. H. Han (International Journal of Environmental Science and Technology, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

Gaseous environment modulates volatile emission and viability loss during seed artificial ageing - Biao Han; Vincent Fernandez; Hugh W. Pritchard; Louise Colville (Planta, 2021)
Main conclusion Modulation of the gaseous environment using oxygen absorbers and/or silica gel shows potential for enhancing seed longevity through trapping toxic volatiles emitted by seeds during artificial ageing. Abstract Volatile profiling using non-invasive gas chromatography–mass spectrometry provides insight into the specific processes occurring during seed ageing. Production of alcohols, aldehydes and ketones, derived from processes such as alcoholic fermentation, lipid peroxidation and Maillard reactions, are known to be dependent on storage temperature and relative humidity, but little is known about the potential modulating role of the gaseous environment, which also affects seed lifespan, on volatile production. Seeds of Lolium perenne (Poaceae), Agrostemma githago (Caryophyllaceae) and Pisum sativum (Fabaceae) were aged under normal atmospheric oxygen conditions and in sealed vials containing either oxygen absorbers, oxygen absorbers and silica gel (equilibrated at 60% RH), or silica gel alone. Seeds of A. githago that were aged in the absence of oxygen maintained higher viability and produced fewer volatiles than seeds aged in air. In addition, seeds of A. githago and L. perenne aged in the presence of silica gel were longer lived than those aged without silica, with no effect on seed moisture content or oxygen concentration in the storage containers, but with silica gel acting as a volatile trap. These results indicate that the use of inexpensive oxygen absorbers and silica gel could improve seed longevity in storage for some species and suggests a potential, and previously unidentified, role for silica gel in ultra-dry storage.

Changes in arthropod community but not plant quality benefit a specialist herbivore on plants under reduced water availability - Po-An Lin; Chia-Ming Liu; Jia-Ang Ou; Cheng-Han Sun; Wen-Po Chuang; Chuan-Kai Ho; Natsuko Kinoshita; Gary W. Felton (Oecologia, 2021)

Dissociable dopaminergic and pavlovian influences in goal-trackers and sign-trackers on a model of compulsive checking in OCD - D. M. Eagle; C. Schepisi; S. Chugh; S. Desai; S. Y. S. Han; T. Huang; J. J. Lee; C. Sobala; W. Ye; A. L. Milton; T. W. Robbins (Psychopharmacology, 2020)
Rationale Checking is a functional behaviour that provides information to guide behaviour. However, in obsessive-compulsive disorder (OCD), checking may escalate to dysfunctional levels. The processes underpinning the transition from functional to dysfunctional checking are unclear but may be associated with individual differences that support the development of maladaptive behaviour. We examined one such predisposition, sign-tracking to a pavlovian conditioned stimulus, which we previously found associated with dysfunctional checking. How sign-tracking interacts with another treatment with emerging translational validity for OCD-like checking, chronic administration of the dopamine D 2 receptor agonist quinpirole, is unknown. Objectives We tested how functional and dysfunctional checking in the rat observing response task (ORT) was affected by chronic quinpirole administration in non-autoshaped controls and autoshaped animals classified as sign-trackers or goal-trackers. Methods Sign-trackers or goal-trackers were trained on the ORT before the effects of chronic quinpirole administration on checking were assessed. Subsequently, the effects on checking of different behavioural challenges, including reward omission and the use of unpredictable reinforcement schedules, were tested. Results Prior autoshaping increased checking. Sign-trackers and goal-trackers responded differently to quinpirole sensitization, reward omission and reinforcement uncertainty. Sign-trackers showed greater elevations in dysfunctional checking, particularly during uncertainty. By contrast, goal-trackers predominantly increased functional checking responses, possibly in response to reduced discrimination accuracy in the absence of cues signalling which lever was currently active. Conclusions The results are discussed in terms of how pavlovian associations influence behaviour that becomes compulsive in OCD and how this may be dependent on striatal dopamine D 2 receptors.

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Carbon accumulation in agroforestry systems is affected by tree species diversity, age and regional climate: A global meta‐analysis - Zilong Ma; Han Y. H. Chen; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang (Global Ecology and Biogeography, 2020)
Aim Agroforestry is a globally practised system of land use for achieving greater and more diverse biomass production, but it has other ecological benefits, such as mitigation of climate change. Despite this, long‐term carbon (C) accumulation in different components of agroforestry systems, the drivers for C accumulation and the linkages between tree biomass and soil C stocks remain unclear. Location Global. Time period From 1989 to 2019. Major taxa studied Trees. Methods Here, we report on a global meta‐analysis based on 141 studies to identify patterns of C accumulation in tree‐based agroforestry systems compared with sole cropland and pasture. Results We found that agroforestry systems had, on average, 46.1 Mg/ha (95% confidence interval, 36.4–55.8 Mg/ha) more C in tree biomass compared with sole cropland‐ or pasture‐based land uses without trees. Furthermore, agroforestry systems with multiple tree species contained greater biomass C stocks and accumulated biomass C faster than systems with a single tree species. The effect of agroforestry practices on soil C stock increased with tree age, although such increases varied among climatic zones. Agroforestry systems in tropical zones had the ability to increase soil C to peak levels quickly, whereas soil C in temperate zones increased at a slower rate but peaked at a greater overall soil C level. Our structural equation model did not detect a direct linkage between biomass C and changes in total soil C stock in agroforestry systems. Main conclusions Our results demonstrate that planting multiple tree species in agroforestry systems is an important strategy to increase biomass C sequestration, with regional climate affecting the temporal change of soil C in response to agroforestry practices.

Discovery of numerous pingos and comet-shaped depressions offshore southwestern Taiwan - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Ingo Klaucke; Ho-Han Hsu; Chih-Chieh Su; Roberto Gwiazda; David W. Caress (Geo-Marine Letters, 2020)

Characterization of urinary concentrations of heavy metals among socioeconomically disadvantaged black pregnant women - Inkyu Han; Kristina W. Whitworth; Xueying Zhang; Masoud Afshar; Pamela D. Berens; Elaine Symanski (Environmental Monitoring and Assessment, 2020)
The objective of this study was to characterize exposures to metals using biological samples collected on socioeconomically disadvantaged black pregnant women. We obtained 131 anonymous urine samples provided by black pregnant women visiting a Medicaid-serving prenatal clinic in Houston, TX, from March 27, 2017 to April 11, 2017. We analyzed urine samples for 15 metals including cadmium (Cd), arsenic (As), lead (Pb), and nickel (Ni) and for creatinine and cotinine. We found that median concentrations of zinc (Zn), selenium (Se), and aluminum (Al) among black pregnant women in this study were 1.5 to 3 times higher than levels reported among a cohort of well-educated non-Hispanic white pregnancy planners. We also observed elevated levels of urinary Cd and antimony (Sb) as compared with those reported for a nationally representative sample of adult women in the USA. Based on the results of an exploratory factor analysis, potential sources of metal exposures in this population may arise in home environments or be due to diet, industrial and natural sources, or traffic.

Stochastic sediment transport: anomalous diffusions and random movement - Christina W. Tsai; Serena Y. Hung; Tsung-Han Wu (Stochastic Environmental Research and Risk Assessment, 2020)

Stem Cell Mechanosensation on Gelatin Methacryloyl (GelMA) Stiffness Gradient Hydrogels - Claire Kim; Jennifer L. Young; Andrew W. Holle; Kwanghee Jeong; Luke G. Major; Ji Hoon Jeong; Zachary M. Aman; Dong-Wook Han; Yongsung Hwang; Joachim P. Spatz; Yu Suk Choi (Annals of Biomedical Engineering, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Do breast quadrants explain racial disparities in breast cancer outcomes? - Yunan Han; Justin Xavier Moore; Marvin Langston; Lindsay Fuzzell; Saira Khan; Marquita W. Lewis; Graham A. Colditz; Ying Liu (Cancer Causes & Control, 2019)

Plants alter their vertical root distribution rather than biomass allocation in response to changing precipitation - Bingwei Zhang; Marc W. Cadotte; Shiping Chen; Xingru Tan; Cuihai You; Tingting Ren; Minling Chen; Shanshan Wang; Weijing Li; Chengjin Chu; Lin Jiang; Yongfei Bai; et al. (Ecology, 2019)
Elucidating the variation of allocation pattern of ecosystem net primary productivity ( NPP ) and its underlying mechanisms is critically important for understanding the changes of aboveground and belowground ecosystem functions. Under optimal partitioning theory, plants should allocate more NPP to the organ that acquires the most limiting resource, and this expectation has been widely used to explain and predict NPP allocation under changing precipitation. However, confirmatory evidence for this theory has mostly come from observed spatial variation in the relationship between precipitation and NPP allocation across ecosystems, rather than directly from the influences of changing precipitation on NPP allocation within systems. We performed a 6‐yr five‐level precipitation manipulation experiment in a semiarid steppe to test whether changes in NPP allocation can be explained by the optimal partitioning theory, and how water requirement of plant community is maintained if NPP allocation is unaltered. The 30 precipitation levels (5 levels × 6 yr) were divided into dry, nominal, and wet precipitation ranges, relative to historical precipitation variation over the past six decades. We found that NPP in both aboveground ( ANPP ) and belowground ( BNPP ) increased nonlinearly as precipitation increased, while the allocation of NPP to BNPP ( f BNPP ) showed a concave quadratic relationship with precipitation. The declined f BNPP as precipitation increased in the dry range supported the optimal partitioning theory. However, in the nominal range, NPP allocation was not influenced by the changed precipitation; instead, BNPP was distributed more in the surface soil horizon (0–10 cm) as precipitation increased, and conversely more in the deeper soil layers (10–30 cm) as precipitation decreased. This response in root foraging appears to be a strategy to satisfy plant water requirements and partially explains the stable NPP allocation patterns. Overall, our results suggest that plants can adjust their vertical BNPP distribution in response to drought stress, and that only under extreme drought does the optimal partitioning theory strictly apply, highlighting the context dependency of the adaption and growth of plants under changing precipitation.

COL4A1 mutations as a potential novel cause of autosomal dominant CAKUT in humans - Thomas M. Kitzler; Ronen Schneider; Stefan Kohl; Caroline M. Kolvenbach; Dervla M. Connaughton; Rufeng Dai; Nina Mann; Makiko Nakayama; Amar J. Majmundar; Chen-Han W. Wu; Jameela A. Kari; Sherif M. El Desoky; et al. (Human Genetics, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Local Application of Autologous Platelet-Rich Fibrin Patch (PRF-P) Suppresses Regulatory T Cell Recruitment in a Murine Glioma Model - Wojciech K. Panek; Katarzyna C. Pituch; Jason Miska; Julius W. Kim; Aida Rashidi; Deepak Kanojia; Aurora Lopez-Rosas; Yu Han; Dou Yu; Catalina Lee Chang; J. Robert Kane; Peng Zhang; et al. (Molecular Neurobiology, 2019)

A Sustained Ocean Observing System in the Indian Ocean for Climate Related Scientific Knowledge and Societal Needs - J. C. Hermes; Y. Masumoto; L. M. Beal; M. K. Roxy; J. Vialard; M. Andres; H. Annamalai; S. Behera; N. D’Adamo; T. Doi; M. Feng; W. Han; et al. (Frontiers in Marine Science, 2019)

Neuronal nitric oxide synthase activity mediates Lycium barbarum polysaccharides-enhanced sexual performance without stimulating noncontact erection in rats - Andy C. Huang; Jia-Min Wu; Ya-Han Chang; Navneet Kumar Dubey; Allen W. Chiu; Chien-Yu Yeh; Tung-Hu Tsai; Kuei-Ying Yeh (Psychopharmacology, 2019)

The Role of Deimination in Regenerative Reprogramming of Neurons - Di Ding; Mabel Enriquez-Algeciras; Anddre Osmar Valdivia; Juan Torres; Cameron Pole; John W Thompson; Tsung-han Chou; Miguel Perez-Pinzon; Vittorio Porciatti; Susan Udin; Eric Nestler; Sanjoy K. Bhattacharya (Molecular Neurobiology, 2019)

Ocean acidification increases iodine accumulation in kelp‐based coastal food webs - Dong Xu; Georgina Brennan; Le Xu; Xiao W. Zhang; Xiao Fan; Wen T. Han; Thomas Mock; Andrew McMinn; David A. Hutchins; Naihao Ye (Global Change Biology, 2019)
Kelp are main iodine accumulators in the ocean, and their growth and photosynthesis are likely to benefit from elevated seawater CO 2 levels due to ocean acidification. However, there are currently no data on the effects of ocean acidification on iodine metabolism in kelp. As key primary producers in coastal ecosystems worldwide, any change in their iodine metabolism caused by climate change will potentially have important consequences for global geochemical cycles of iodine, including iodine levels of coastal food webs that underpin the nutrition of billions of humans around the world. Here, we found that elevated p CO 2 enhanced growth and increased iodine accumulation not only in the model kelp Saccharina japonica using both short‐term laboratory experiment and long‐term in situ mesocosms, but also in several other edible and ecologically significant seaweeds using long‐term in situ mesocosms. Transcriptomic and proteomic analysis of S. japonica revealed that most vanadium‐dependent haloperoxidase genes involved in iodine efflux during oxidative stress are down‐regulated under increasing p CO 2 , suggesting that ocean acidification alleviates oxidative stress in kelp, which might contribute to their enhanced growth. When consumed by abalone ( Haliotis discus), elevated iodine concentrations in S. japonica caused increased iodine accumulation in abalone, accompanied by reduced synthesis of thyroid hormones. Thus, our results suggest that kelp will benefit from ocean acidification by a reduction in environmental stress however; iodine levels, in kelp‐based coastal food webs will increase, with potential impacts on biogeochemical cycles of iodine in coastal ecosystems.

Forward modelling of global gravity fields with 3D density structures and an application to the high-resolution (~ 2 km) gravity fields of the Moon - M. Šprlák; S.-C. Han; W. E. Featherstone (Journal of Geodesy, 2018)

Unexpected dietary preferences of Eurasian Spoonbills in the Dutch Wadden Sea: spoonbills mainly feed on small fish not shrimp - Jeltje Jouta; Petra de Goeij; Tamar Lok; Estefania Velilla; Cornelis J. Camphuysen; Mardik Leopold; Henk W. van der Veer; Han Olff; Otto Overdijk; Theunis Piersma (Journal of Ornithology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Observed and modelled temperature and precipitation extremes over Southeast Asia from 1972 to 2010 - W. K. Cheong; B. Timbal; N. Golding; S. Sirabaha; K. F. Kwan; T. A. Cinco; B. Archevarahuprok; V. H. Vo; D. Gunawan; S. Han (International Journal of Climatology, 2018)
Regional assessments of trends in climate extremes are necessary for countries to make informed decisions about adaptation strategies and to put these changes into a global context. A workshop bringing together several Southeast Asian countries has delivered a new set of daily weather observations suitable to analyse the changes in temperature and precipitation extremes between 1972 and 2010. The use of a consistent and widely tested methodology in this study allows a direct comparison with results from other parts of the world. Trends in a range of climate extremes indices were assessed focusing on spatial variation in these trends. For most locations temperature trends obtained in this study appear broadly consistent with previous assessments; for some locations stronger trends have been detected through the inclusion of new data. In contrast to earlier studies, evidence of trends in precipitation extremes is emerging, with significant increasing trends in both regional and subregional data. In addition, large correlations between regional rainfall extremes and large‐scale features such as El Niño‐Southern Oscillation and the Indian Ocean Dipole were identified. Finally, the observed trends are compared with a regional climate model reconstruction of the historical period. It was found that the model captures very well the trends and spatial variation of temperature extremes across the region, albeit with an underestimation of the more extreme indices. In contrast, the trends in precipitation extremes are largely overestimated, particularly in the western side of Southeast Asia.

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Hemodynamic assessments of the ascending thoracic aortic aneurysm using fluid-structure interaction approach - Han Hung Yeh; Simon W. Rabkin; Dana Grecov (Medical & Biological Engineering & Computing, 2018)

Relative impacts of light, temperature, and reactive oxygen on thaumarchaeal ammonia oxidation in the North Pacific Ocean - Rachel E. A. Horak; Wei Qin; Anthony D. Bertagnolli; Alexa Nelson; Katherine R. Heal; Hantten Han; Maija Heller; Andrew J. Schauer; Wade H. Jeffrey; E. Virginia Armbrust; James W. Moffett; Anitra E. Ingalls; et al. (Limnology and Oceanography, 2018)
Thaumarchaeota are implicated as the major ammonia oxidizers in the ocean. However, the influence of various abiotic factors in determining their distribution and activity in the upper ocean remain largely unclear. Here, we examined the influence of light, hydrogen peroxide (H 2 O 2 ), and temperature on ammonia oxidation rates for communities dominated by Thaumarchaeota at the nitrite maximum across two North Pacific transects. In situ ammonia oxidation was almost exclusively driven by Thaumarchaeota , as inferred from ammonia monooxygenase subunit A ( amoA ) genes, amoA transcripts, and inhibitor studies. A major shift in population structure near the eastern North Pacific Subtropical Front was revealed by sequence variation of amoA genes, showing different Thaumarchaeota community structure in oligotrophic gyre and temperate regions. While the most dominant OTUs were closely related, we found significant differences in physiological responses to light and temperature of incubation. At four stations in different biogeochemical regimes, the impact of sunlight intensity and temperature on activity was evaluated using 15 ‐spiked whole seawater collected from the nitrite maximum and incubated at different depths on a free floating in situ array. Ammonia oxidation was usually completely inhibited by PAR at the surface and 21–45% inhibited at 1% surface PAR, whereas a temperature effect on ammonia oxidation was observed at only two of four stations. While inhibition due to H 2 O 2 cannot be ruled out in surface waters, our findings show that below the mixed layer, photoinhibition, and not H 2 O 2 toxicity, had a greater influence on ammonia oxidation.

Fungal Denitrification Activity in Vertical Flow Constructed Wetlands as Impacted by Plant Species Richness, Carbon, Nitrogen and pH Amendments - W. L. Liu; C. B. Zhang; W. J. Han; M. Guan; S. Y. Liu; Y. Ge; J. Chang (Bulletin of Environmental Contamination and Toxicology, 2017)

Ammonia‐oxidising archaea living at low pH: Insights from comparative genomics - Craig W. Herbold; Laura E. Lehtovirta‐Morley; Man‐Young Jung; Nico Jehmlich; Bela Hausmann; Ping Han; Alexander Loy; Michael Pester; Luis A. Sayavedra‐Soto; Sung‐Keun Rhee; James I. Prosser; Graeme W. Nicol; et al. (Environmental Microbiology, 2017)
Summary Obligate acidophilic members of the thaumarchaeotal genus Candidatus Nitrosotalea play an important role in nitrification in acidic soils, but their evolutionary and physiological adaptations to acidic environments are still poorly understood, with only a single member of this genus ( Ca . N. devanaterra) having its genome sequenced. In this study, we sequenced the genomes of two additional cultured Ca . Nitrosotalea strains, extracted an almost complete Ca . Nitrosotalea metagenome‐assembled genome from an acidic fen, and performed comparative genomics of the four Ca . Nitrosotalea genomes with 19 other archaeal ammonia oxidiser genomes. Average nucleotide and amino acid identities revealed that the four Ca . Nitrosotalea strains represent separate species within the genus. The four Ca . Nitrosotalea genomes contained a core set of 103 orthologous gene families absent from all other ammonia‐oxidizing archaea and, for most of these gene families, expression could be demonstrated in laboratory culture or the environment via proteomic or metatranscriptomic analyses respectively. Phylogenetic analyses indicated that four of these core gene families were acquired by the Ca . Nitrosotalea common ancestor via horizontal gene transfer from acidophilic representatives of Euryarchaeota. We hypothesize that gene exchange with these acidophiles contributed to the competitive success of the Ca . Nitrosotalea lineage in acidic environments.

Removal of Cr(VI) and phenol coupled with the reduction of sulfate by sulfate-reducing bacteria sludge - X. Han; T.-X. Zhou; S.-W. Xu; Y. Li; Y.-F. Wang; Y. Liu (International Journal of Environmental Science and Technology, 2017)

Transgenic Mice Overexpressing the Divalent Metal Transporter 1 Exhibit Iron Accumulation and Enhanced Parkin Expression in the Brain - Cheng-Wu Zhang; Yee Kit Tai; Bing-Han Chai; Katherine C. M. Chew; Eng-Tat Ang; Fai Tsang; Bryce W. Q. Tan; Eugenia T. E. Hong; Abu Bakar Ali Asad; Kai-Hsiang Chuang; Kah-Leong Lim; Tuck Wah Soong (NeuroMolecular Medicine, 2017)

The Contribution of Litterfall to Net Primary Production During Secondary Succession in the Boreal Forest - Han Y. H. Chen; Amber N. Brant; Meelis Seedre; Brian W. Brassard; Anthony R. Taylor (Ecosystems, 2017)

Global Mammal Parasite Database version 2.0 - Patrick R. Stephens; Paula Pappalardo; Shan Huang; James E. Byers; Maxwell J. Farrell; Alyssa Gehman; Ria R. Ghai; Sarah E. Haas; Barbara Han; Andrew W. Park; John P. Schmidt; Sonia Altizer; et al. (Ecology, 2017)
Illuminating the ecological and evolutionary dynamics of parasites is one of the most pressing issues facing modern science, and is critical for basic science, the global economy, and human health. Extremely important to this effort are data on the disease‐causing organisms of wild animal hosts (including viruses, bacteria, protozoa, helminths, arthropods, and fungi). Here we present an updated version of the Global Mammal Parasite Database, a database of the parasites of wild ungulates (artiodactyls and perissodactyls), carnivores, and primates, and make it available for download as complete flat files. The updated database has more than 24,000 entries in the main data file alone, representing data from over 2700 literature sources. We include data on sampling method and sample sizes when reported, as well as both “reported” and “corrected” (i.e., standardized) binomials for each host and parasite species. Also included are current higher taxonomies and data on transmission modes used by the majority of species of parasites in the database. In the associated metadata we describe the methods used to identify sources and extract data from the primary literature, how entries were checked for errors, methods used to georeference entries, and how host and parasite taxonomies were standardized across the database. We also provide definitions of the data fields in each of the four files that users can download.

Ectomycorrhizal fungal response to warming is linked to poor host performance at the boreal‐temperate ecotone - Christopher W. Fernandez; Nhu H. Nguyen; Artur Stefanski; Ying Han; Sarah E. Hobbie; Rebecca A. Montgomery; Peter B. Reich; Peter G. Kennedy (Global Change Biology, 2017)
Rising temperatures associated with climate change have been shown to negatively affect the photosynthetic rates of boreal forest tree saplings at their southern range limits. To quantify the responses of ectomycorrhizal ( EM ) fungal communities associated with poorly performing hosts, we sampled the roots of Betula papyrifera and Abies balsamea saplings growing in the B4Warmed (Boreal Forest Warming at an Ecotone in Danger) experiment. EM fungi on the root systems of both hosts were compared from ambient and +3.4 °C air and soil warmed plots at two sites in northern Minnesota. EM fungal communities were assessed with high‐throughput sequencing along with measures of plant photosynthesis, soil temperature, moisture, and nitrogen. Warming selectively altered EM fungal community composition at both the phylum and genus levels, but had no significant effect on EM fungal operational taxonomic unit ( OTU ) diversity. Notably, warming strongly favored EM Ascomycetes and EM fungi with short‐contact hyphal exploration types. Declining host photosynthetic rates were also significantly inversely correlated with EM Ascomycete and EM short‐contact exploration type abundance, which may reflect a shift to less carbon demanding fungi due to lower photosynthetic capacity. Given the variation in EM host responses to warming, both within and between ecosystems, better understanding the link between host performance and EM fungal community structure will to clarify how climate change effects cascade belowground.

Species-rich grassland can persist under nitrogen-rich but phosphorus-limited conditions - Han F. van Dobben; G. W. Wieger Wamelink; Pieter A. Slim; Jan Kamiński; Hubert Piórkowski (Plant and Soil, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

Altered tooth morphogenesis after silencing the planar cell polarity core component, Vangl2 - Zhaoming Wu; Don Jeevanie Epasinghe; Jinquan He; Liwen Li; David W. Green; Min-Jung Lee; Han-Sung Jung (Cell and Tissue Research, 2016)

Induced growth promotion and higher salt tolerance in the halophyte grass Puccinellia tenuiflora by beneficial rhizobacteria - Shu-Qi Niu; Hui-Ru Li; Paul W. Paré; Mina Aziz; Suo-Min Wang; Huazhong Shi; Jing Li; Qing-Qing Han; Shi-Qian Guo; Jian Li; Qiang Guo; Qing Ma; et al. (Plant and Soil, 2016)

Outbreak of hirame rhabdovirus infection in cultured spotted sea bass Lateolabrax maculatus on the western coast of Korea - H‐G Seo; J W Do; S H Jung; H‐J Han (Journal of Fish Diseases, 2016)
In this study, we determined the cause of a disease outbreak in spotted sea bass, Lateolabrax maculatus reared in culture cages on the western coast of Korea in 2013. The major signs in the diseased fish exhibited were haemorrhaging on the membranes of the abdomen, gastrointestinal organs and opercular gills, as well as an enlarged spleen. No external morphological signs of infection were visible, except for a darkening in colour. No parasites or pathological bacteria were isolated from the diseased fish; however, epithelioma papulosum cyprini ( EPC ) cells inoculated with tissue homogenates from the diseased fish showed cytopathic effects ( CPE s). Virus particles in the EPC cells were bullet‐shaped, 185–225 nm long and 70–80 nm wide, characteristic of Rhabdoviridae. Polymerase chain reaction analyses of homogenized tissues from the diseased fish and supernatants of cell cultures with CPE s indicated specific, 553‐bp‐long fragments corresponding to the matrix protein gene of the hirame rhabdovirus ( HIRRV ). Phylogenetically, the HIRRV phosphoprotein gene of spotted sea bass was more closely related to phosphoproteins from Chinese and Polish HIRRV strains than from other Korean strains. To our knowledge, this is the first report of HIRRV infection in cultured spotted sea bass.

Synthesis and accumulation of glutenin subunits during grain development in bread wheat as revealed by reversed-phase ultra-performance liquid chromatography (RP-UPLC) - J. Zhou; W. Liu; C. Han; H. Cao; Y. Xu; W. Zhang; Y. Yan (Cereal Research Communications, 2016)

Enhanced bioremoval of refractory compounds from dyeing wastewater using optimized sequential anaerobic/aerobic process - W. Bae; D. Han; E. Kim; R. A. de Toledo; K. Kwon; H. Shim (International Journal of Environmental Science and Technology, 2016)

Effects of 4-methylbenzylidene camphor (4-MBC) on neuronal and muscular development in zebrafish (Danio rerio) embryos - Vincent Wai Tsun Li; Mei Po Mirabelle Tsui; Xueping Chen; Michelle Nga Yu Hui; Ling Jin; Raymond H. W. Lam; Richard Man Kit Yu; Margaret B. Murphy; Jinping Cheng; Paul Kwan Sing Lam; Shuk Han Cheng (Environmental Science and Pollution Research, 2016)

On the stability of colonnade structural systems under static and dynamic loading conditions - V. Sarhosis; P. Asteris; T. Wang; W. Hu; Y. Han (Bulletin of Earthquake Engineering, 2016)

Scaffolding during the cell cycle by A-kinase anchoring proteins - B. Han; W. J. Poppinga; M. Schmidt (Pflügers Archiv - European Journal of Physiology, 2015)

High-density mapping of the major FHB resistance gene Fhb7 derived from Thinopyrum ponticum and its pyramiding with Fhb1 by marker-assisted selection - Jun Guo; Xiuli Zhang; Yanlin Hou; Jinjin Cai; Xiaorong Shen; Tingting Zhou; Huihui Xu; Herbert W. Ohm; Hongwei Wang; Anfei Li; Fangpu Han; Honggang Wang; et al. (Theoretical and Applied Genetics, 2015)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

The Fresnel–Fizeau effect and the atmospheric time delay in geodetic VLBI - S. M. Kopeikin; W.-B. Han (Journal of Geodesy, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Effect of repeated exposures and sociality on novel food acceptance and consumption by orangutans - Madeleine E. Hardus; Adriano R. Lameira; Serge A. Wich; Han de Vries; Rachmad Wahyudi; Robert W. Shumaker; Steph B. J. Menken (Primates, 2015)

Health Literacy and Pap Testing in Insured Women - K. M. Mazor; A. E. Williams; D. W. Roblin; B. Gaglio; S. L. Cutrona; M. E. Costanza; P. K. J. Han; J. L. Wagner; H. Fouayzi; T. S. Field (Journal of Cancer Education, 2014)

Limited diagnostic value of microsatellite instability associated pathology features in colorectal cancer - Paul G. van Putten; Margot G. F. van Lier; Mariska Hage; Katharina Biermann; Reinier H. van Rijssel; Pieter J. Westenend; Hans Morreau; Ewout W. Steyerberg; Winand N. M. Dinjens; Ernst J. Kuipers; Monique E. van Leerdam; J. Han van Krieken (Familial Cancer, 2014)

Recovery of Ecosystem Carbon Stocks in Young Boreal Forests: A Comparison of Harvesting and Wildfire Disturbance - Meelis Seedre; Anthony R. Taylor; Brian W. Brassard; Han Y. H. Chen; Kalev Jõgiste (Ecosystems, 2014)

Decline in Net Ecosystem Productivity Following Canopy Transition to Late-Succession Forests - Anthony R. Taylor; Meelis Seedre; Brian W. Brassard; Han Y. H. Chen (Ecosystems, 2014)

Effects of Transduction of the bcl-2 Gene and of Nerve Growth Factor on Apoptosis of Cultured PC12 Cells - G. Han; W. Wei; X. Zhang; Zh. Lai; Ch. Chen (Neurophysiology, 2014)

Synergistic Inhibition on Acetylcholinesterase by the Combination of Berberine and Palmatine Originally Isolated from Chinese Medicinal Herbs - Shinghung Mak; Wilson W. K. Luk; Wei Cui; Shengquan Hu; Karl W. K. Tsim; Yifan Han (Journal of Molecular Neuroscience, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Cellular mechanisms in intermittent hypoxia-induced cardiac damage in vivo - Qian Han; Sze C. Yeung; Mary S. M. Ip; Judith C. W. Mak (Journal of Physiology and Biochemistry, 2014)

Keratinocyte growth factor and thiazolidinediones and linolenic acid differentiate characterized mammary fat pad adipose stem cells isolated from prepubertal Korean black goat to epithelial and adipogenic lineage - A. M. M. T Reza; S. Shiwani; N. K. Singh; J. D. Lohakare; S. J. Lee; D. K. Jeong; J. Y. Han; D. Rengaraj; B. W. Lee (In Vitro Cellular & Developmental Biology - Animal, 2014)

The value of multiple earthquake missions: the EEFIT L’Aquila Earthquake experience - T. Rossetto; D. D’Ayala; F. Gori; R. Persio; J. Han; V. Novelli; S. M. Wilkinson; D. Alexander; M. Hill; S. Stephens; S. Kontoe; G. Elia; et al. (Bulletin of Earthquake Engineering, 2014)

Applications of capillary electrophoresis for rapidly separating and characterizing water-soluble proteins of wheat grains - C. Han; Z. Yu; S. Feng; D. Lv; X. Yan; G. Chen; X. Li; W. Ma; Y. Yan (Cereal Research Communications, 2013)

Non-trophic Interactions Control Benthic Producers on Intertidal Flats - Serena Donadi; Joëlle Westra; Ellen J. Weerman; Tjisse van der Heide; Els M. van der Zee; Johan van de Koppel; Han Olff; Theunis Piersma; Henk W. van der Veer; Britas Klemens Eriksson (Ecosystems, 2013)

Copper requirements of the ammonia‐oxidizing archaeon Nitrosopumilus maritimus SCM1 and implications for nitrification in the marine environment - Shady A. Amin; James W. Moffett; Willm Martens-Habbena; Jeremy E. Jacquot; Yang Han; Allan Devol; Anitra E. Ingalls; David A. Stahl; E. Virginia Armbrust (Limnology and Oceanography, 2013)
Ammonia oxidizing archaea (AOA) have recently been recognized as the primary nitrifiers in the marine environment; they thus play an important role in the nitrogen cycle. Available genome sequences of AOA indicate that numerous Cu‐dependent enzymes are essential for both ammonia oxidation and electron transfer, suggesting a particularly high requirement for copper. However, our knowledge of the copper requirements of AOA and their response to copper limitation in the ocean is nonexistent. Here, we examine the copper requirements of the chemolithoautotrophic AOA Candidatus Nitrosopumilus maritimus SCM1 using a combination of the metal chelators ethylenediaminetetraacetic acid and 1,4,8,11‐tetraazacyclotetradecane‐1,4,8,11‐tetraacetic acid and show that ammonia oxidation is limited at free cupric ion concentrations −12.7 mol L −1 , which are higher than concentrations frequently reported for many coastal and oceanic regimes. Prolonged exposure of cells to copper starvation for up to 6 d had no effect on the recovery of ammonia oxidation by N. maritimus. In addition, we present evidence that N. maritimus does not produce a copper‐binding ligand (chalkophore) under copper limitation and therefore probably relies mainly on acquisition of copper ions from surrounding media. Copper limitation may be an important constraint on archaeal ammonia oxidation throughout the marine environment.

Systematic overestimation of Salicaceae seed survival using radicle emergence in response to drying and storage: implications for ex situ seed banking - Elena V. Popova; Du Hyun Kim; Sim Hee Han; Elena Moltchanova; Hugh W. Pritchard; Yong Pyo Hong (Acta Physiologiae Plantarum, 2013)

Stability of Soil Carbon Stocks Varies with Forest Composition in the Canadian Boreal Biome - Jérôme Laganière; David Paré; Yves Bergeron; Han Y. H. Chen; Brian W. Brassard; Xavier Cavard (Ecosystems, 2013)

Artery Buckling: New Phenotypes, Models, and Applications - Hai-Chao Han; Jennifer K. W. Chesnutt; Justin R. Garcia; Qin Liu; Qi Wen (Annals of Biomedical Engineering, 2013)

Pathogenesis of type 1 (European genotype) porcine reproductive and respiratory syndrome virus in male gonads of infected boar - K. Han; H. W. Seo; Y. Oh; I. Kang; C. Park; J. H. Han; S.-H. Kim; C. Chae (Veterinary Research Communications, 2013)

Photocatalytic degradation of contaminants of concern with composite NF-TiO2 films under visible and solar light - H. Barndõk; M. Peláez; C. Han; W. E. Platten; P. Campo; D. Hermosilla; A. Blanco; D. D. Dionysiou (Environmental Science and Pollution Research, 2013)

Study of chloropropanols in soy sauce by gas chromatography-triple quadrupole mass spectrometry with coupled column separation without derivatisation - X.-M. Xu; H.-W. Wu; H.-L. He; B.-F. Huang; J.-L. Han; Y.-P. Ren (Food Additives & Contaminants: Part A, 2013)

Fruit production in three masting tree species does not rely on stored carbon reserves - Günter Hoch; Rolf T. W. Siegwolf; Sonja G. Keel; Christian Körner; Qingmin Han (Oecologia, 2013)

Apoptosis initiation of β-ionone in SGC-7901 gastric carcinoma cancer cells via a PI3K-AKT pathway - Qian Liu; Hong-Wei Dong; Wen-Guang Sun; Ming Liu; Juan C. Ibla; Lian-Xin Liu; John W. Parry; Xiao-Hui Han; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Effect of cholesterol on lipogenesis and VLDL–TG assembly and secretion in goose primary hepatocytes - C. C. Han; J. W. Wang; Z. X. Pan; H. Tang; S. X. Xiang; J. Wang; L. Li; F. Xu; S. H. Wei (Molecular and Cellular Biochemistry, 2013)

Enhanced drought and salt tolerance by expression of AtGSK1 gene in poplar - M. S. Han; E. W. Noh; S. H. Han (Plant Biotechnology Reports, 2013)

Co-expression of soybean Dicer-like genes in response to stress and development - Shaun J. Curtin; Michael B. Kantar; Han W. Yoon; Adam M. Whaley; Jessica A. Schlueter; Robert M. Stupar (Functional & Integrative Genomics, 2012)

Desulfohalophilus alkaliarsenatis gen. nov., sp. nov., an extremely halophilic sulfate- and arsenate-respiring bacterium from Searles Lake, California - Jodi Switzer Blum; Thomas R. Kulp; Sukkyun Han; Brian Lanoil; Chad W. Saltikov; John F. Stolz; Laurence G. Miller; Ronald S. Oremland (Extremophiles, 2012)

Agronomic Considerations for Sweet Sorghum Biofuel Production in the South-Central USA - K. J. Han; W. D. Pitman; M. W. Alison; D. L. Harrell; H. P. Viator; M. E. McCormick; K. A. Gravois; M. Kim; D. F. Day (BioEnergy Research, 2012)

Adsorption of bisphenol A on lignin: effects of solution chemistry - W. Han; L. Luo; S. Zhang (International Journal of Environmental Science and Technology, 2012)

Spatially Extended Habitat Modification by Intertidal Reef-Building Bivalves has Implications for Consumer-Resource Interactions - Els M. van der Zee; Tjisse van der Heide; Serena Donadi; Johan S. Eklöf; Britas Klemens Eriksson; Han Olff; Henk W. van der Veer; Theunis Piersma (Ecosystems, 2012)

Isolation and Characterization of a Lytic Myoviridae Bacteriophage PAS-1 with Broad Infectivity in Aeromonas salmonicida - J. H. Kim; J. S. Son; Y. J. Choi; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; D. H. Kang; C. Oh; S. J. Heo; S. C. Park (Current Microbiology, 2012)

Isolation, mapping, SNP detection and association with backfat traits of the porcine CTNNBL1 and DGAT2 genes - Q. Yin; H. -W. Yang; X. -L. Han; B. Fan; B. Liu (Molecular Biology Reports, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Complete genomic sequence of a T4-like bacteriophage, phiAS4, infecting Aeromonas salmonicida subsp. salmonicida - J. H. Kim; J. S. Son; Y. J. Choi; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

Genomic sequence of infectious hypodermal and hematopoietic necrosis virus (IHHNV) KLV-2010-01 originating from the first Korean outbreak in cultured Litopenaeus vannamei - J. H. Kim; H. K. Kim; V. G. Nguyen; B. K. Park; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

Prevalence and different characteristics of two serotypes of Streptococcus parauberis isolated from the farmed olive flounder, Paralichthys olivaceus (Temminck and Schlegel), in Korea - S Y Han; B K Kang; B J Kang; S P Shin; B H Soen; J M Kim; J H Kim; C H Choresca; J E Han; J W Jun; S C Park (Journal of Fish Diseases, 2011)
The prevalence of two serotypes of Streptococcus parauberis isolated from the olive flounder, Paralichthys olivaceus , was evaluated in a total of 29 isolates between 2003 and 2010 in Korea. Streptococcus parauberis isolates were divided into two serologically distinct types (serotype 1 and serotype 2), except for one strain (S1091), using an agglutination assay with rabbit antiserum, and serotype 1 was identified as the dominant type (24 of 29 isolates) in this study. To identify the characteristics of the two serotypes of S. parauberis , we conducted a biochemical test using the API 20 Strep kit, a transmission electron microscopy (TEM) assay, sequence analysis of 16S‐23S rRNA intergenic spacer region (ISR) and a pathogenicity test. In TEM, both serotypes possessed polysaccharide capsule layers around the cell surface when bacterial cells were treated with a homologous serotype of rabbit antiserum. However, we were unable to discriminate serotype‐specific biochemical characteristics and genetic characteristics of 16S‐23S rRNA ISR between the two serotypes. In the pathogenicity test, the serotype 1 strains induced significantly higher mortality than the serotype 2 strains in olive flounder when experimentally inoculated via the intraperitoneal route.

AAPS Workshop Report: Strategies to Address Therapeutic Protein–Drug Interactions during Clinical Development - Sandhya Girish; Steven W Martin; Mark C Peterson; Lei K. Zhang; Hong Zhao; Joseph Balthasar; Raymond Evers; Honghui Zhou; Min Zhu; Lewis Klunk; Chao Han; Eva Gil Berglund; et al. (The AAPS Journal, 2011)

Medical history and the risk of biliary tract cancers in Shanghai, China: implications for a role of inflammation - Gabriella Andreotti; Enju Liu; Yu-Tang Gao; Mahboobeh Safaeian; Asif Rashid; Ming-Chang Shen; Bin-Shen Wang; Jie Deng; Tian-Quian Han; Bai-He Zhang; Ann W. Hsing (Cancer Causes & Control, 2011)

A new total volume model of debris flows with intermittent surges: based on the observations at Jiangjia Valley, southwest China - N. Sh. Chen; Ch. L. Yang; W. Zhou; F. Q. Wei; Z. L. Li; D. Han; G. Sh. Hu (Natural Hazards, 2011)

Atypical Aeromonas salmonicida infection in the black rockfish, Sebastes schlegeli Hilgendorf , in Korea - H‐J Han; D‐Y Kim; W‐S Kim; C‐S Kim; S‐J Jung; M‐J Oh; D‐H Kim (Journal of Fish Diseases, 2011)
Cultured black rockfish, Sebastes schlegeli , suffered mass mortalities during winter 2008 and spring 2009 in Korea, showing clinical signs of ulcer lesions and haemorrhages over their body surface. The aetiological agent was identified as Aeromonas salmonicida (strains RFAS‐1, ‐2 and ‐3), which is a non‐pigmented, slow‐growing bacterium. Phenotypes of RFAS strains showed variation, while 16S rRNA, gyrB , rpoD , dnaJ and recA gene sequences of all the strains were affiliated to A. salmonicida. In particular, vapA gene sequences of the strains were most closely related to one of the five subspecies of A. salmonicida subsp. masoucida (=KCCM 40239 T ). LD 50 values of RFAS‐1 for intraperitoneal and intramuscular injection were 1.5 × 10 5.25 and 1.5 × 10 6.4 cfu/rockfish, respectively. However, A. salmonicida strains KCCM 40239 T and SAS‐1, which originate from masou and chum salmon, respectively, were not pathogenic to black rockfish. RFAS strains, possessing A‐layer protein on their surface, exhibited β‐haemolytic activity against rockfish erythrocytes and capability to survive in rockfish serum, which seem to be associated with virulence.

Nicotinic acetylcholine receptor genes on chromosome 15q25.1 are associated with nicotine and opioid dependence severity - Porat M. Erlich; Stuart N. Hoffman; Margaret Rukstalis; John J. Han; Xin Chu; W. H. Linda Kao; Glenn S. Gerhard; Walter F. Stewart; Joseph A. Boscarino (Human Genetics, 2010)

Sensitivity of MEG and EEG to Source Orientation - Seppo P. Ahlfors; Jooman Han; John W. Belliveau; Matti S. Hämäläinen (Brain Topography, 2010)

Major Changes in the Ecology of the Wadden Sea: Human Impacts, Ecosystem Engineering and Sediment Dynamics - Britas Klemens Eriksson; Tjisse van der Heide; Johan van de Koppel; Theunis Piersma; Henk W. van der Veer; Han Olff (Ecosystems, 2010)

Population structure of the olive flounder ( Paralichthys olivaceus ) in Korea inferred from microsatellite marker analysis - W.‐J. Kim; K.‐K. Kim; H.‐S. Han; B.‐H. Nam; Y.‐O. Kim; H.‐J. Kong; J.‐K. Noh; M. Yoon (Journal of Fish Biology, 2010)
The population structure of olive flounder Paralichthys olivaceus was estimated using nine polymorphic microsatellite (MS) loci in 459 individuals collected from eight populations, including five wild and three hatchery populations in Korea. Genetic variation in hatchery (mean number of alleles per locus, A = 10·2–12·1; allelic richness, A R = 9·3–10·1; observed heterozygosity, H O = 0·766–0·805) and wild (mean number of alleles per locus, A = 11·8–19·6; allelic richness, A R = 10·9–16·1; observed heterozygosity, H O = 0·820–0·888) samples did not differ significantly, suggesting a sufficient level of genetic variation in these well‐managed hatchery populations, which have not lost a substantial amount of genetic diversity. Neighbour‐joining tree and principal component analyses showed that genetic separation between eastern and pooled western and southern wild populations in Korea was probably influenced by restricted gene flow between regional populations due to the barrier effects of sea currents. The pooled western and southern populations are genetically close, perhaps because larval dispersal may depend on warm currents. One wild population (sample from Wando) was genetically divergent from the main distribution, but it was genetically close to hatchery populations, indicating that the genetic composition of the studied populations may be affected by hydrographic conditions and the release of fish stocks. The estimated genetic population structure and potential applications of MS markers may aid in the proper management of P. olivaceus populations.

Genetic variation in N-acetyltransferases 1 and 2, cigarette smoking, and risk of non-Hodgkin lymphoma - Briseis A. Kilfoy; Tongzhang Zheng; Qing Lan; Xuesong Han; Theodore Holford; David W. Hein; Qin Qin; Brian Leaderer; Lindsay M. Morton; Meredith Yeager; Peter Boyle; Ping Zhao; et al. (Cancer Causes & Control, 2010)

Estimated PBDE and PBB Congeners in Soil from an Electronics Waste Disposal Site - H.-M. Wang; Y.-J. Yu; M. Han; S.-W. Yang; Q. li; Y. Yang (Bulletin of Environmental Contamination and Toxicology, 2009)

Genetic testing for Lynch syndrome in the first year of colorectal cancer: a review of the psychological impact - Karin M. Landsbergen; Judith B. Prins; Han G. Brunner; Floris W. Kraaimaat; Nicoline Hoogerbrugge (Familial Cancer, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

Analysis of genetic structure and relationship among nine indigenous Chinese chicken populations by the Structure program - H. F. Li; W. Han; Y. F. Zhu; J. T. Shu; X. Y. Zhang; K. W. Chen (Journal of Genetics, 2009)

Embryogenic tissue initiation and somatic embryogenesis in Fraser fir (Abies fraseir [Pursh] Poir.) - Y. W. Kim; R. Newton; J. Frampton; K.-H. Han (In Vitro Cellular & Developmental Biology - Plant, 2009)

Paraquat resistance in a Lolium rigidum population is governed by one major nuclear gene - Qin Yu; Heping Han; Linh Nguyen; John W. Forster; Stephen B. Powles (Theoretical and Applied Genetics, 2009)

Bacteria beneath the West Antarctic Ice Sheet - Brian Lanoil; Mark Skidmore; John C. Priscu; Sukkyun Han; Wilson Foo; Stefan W. Vogel; Slawek Tulaczyk; Hermann Engelhardt (Environmental Microbiology, 2009)
Summary Subglacial environments, particularly those that lie beneath polar ice sheets, are beginning to be recognized as an important part of Earth's biosphere. However, except for indirect indications of microbial assemblages in subglacial Lake Vostok, Antarctica, no sub‐ice sheet environments have been shown to support microbial ecosystems. Here we report 16S rRNA gene and isolate diversity in sediments collected from beneath the Kamb Ice Stream, West Antarctic Ice Sheet and stored for 15 months at 4°C. This is the first report of microbes in samples from the sediment environment beneath the Antarctic Ice Sheet. The cells were abundant (∼10 7 cells g −1 ) but displayed low diversity (only five phylotypes), likely as a result of enrichment during storage. Isolates were cold tolerant and the 16S rRNA gene diversity was a simplified version of that found in subglacial alpine and Arctic sediments and water. Although in situ cell abundance and the extent of wet sediments beneath the Antarctic ice sheet can only be roughly extrapolated on the basis of this sample, it is clear that the subglacial ecosystem contains a significant and previously unrecognized pool of microbial cells and associated organic carbon that could potentially have significant implications for global geochemical processes.

A mu opioid receptor gene polymorphism (A118G) and naltrexone treatment response in adherent Korean alcohol-dependent patients - Sung-Gon Kim; Cheol-Min Kim; Sam-Wook Choi; Young-Myo Jae; Hae-Gook Lee; Bong-Ki Son; Jeong-Gee Kim; Young-Sung Choi; Han-Oh Kim; Seong-Yeon Kim; David W. Oslin (Psychopharmacology, 2009)

Landscape Planning for Agricultural Nonpoint Source Pollution Reduction III: Assessing Phosphorus and Sediment Reduction Potential - Matthew W. Diebel; Jeffrey T. Maxted; Dale M. Robertson; Seungbong Han; M. Jake Vander Zanden (Environmental Management, 2009)

Ancient behaviors of larval amphibians in response to an emerging fungal pathogen, Batrachochytrium dendrobatidis - Barbara A. Han; Paul W. Bradley; Andrew R. Blaustein (Behavioral Ecology and Sociobiology, 2008)

Effects of Forest Type and Disturbance on Diversity of Coarse Woody Debris in Boreal Forest - Brian W. Brassard; Han Y. H. Chen (Ecosystems, 2008)

The complete genome sequence of Moorella thermoacetica (f. Clostridium thermoaceticum ) - Elizabeth Pierce; Gary Xie; Ravi D. Barabote; Elizabeth Saunders; Cliff S. Han; John C. Detter; Paul Richardson; Thomas S. Brettin; Amaresh Das; Lars G. Ljungdahl; Stephen W. Ragsdale (Environmental Microbiology, 2008)
Summary This paper describes the genome sequence of Moorella thermoacetica (f. Clostridium thermoaceticum ), which is the model acetogenic bacterium that has been widely used for elucidating the Wood–Ljungdahl pathway of CO and CO 2 fixation. This pathway, which is also known as the reductive acetyl‐CoA pathway, allows acetogenic (often called homoacetogenic) bacteria to convert glucose stoichiometrically into 3 mol of acetate and to grow autotrophically using H 2 and CO as electron donors and CO 2 as an electron acceptor. Methanogenic archaea use this pathway in reverse to grow by converting acetate into methane and CO 2 . Acetogenic bacteria also couple the Wood–Ljungdahl pathway to a variety of other pathways to allow the metabolism of a wide variety of carbon sources and electron donors (sugars, carboxylic acids, alcohols and aromatic compounds) and electron acceptors (CO 2 , nitrate, nitrite, thiosulfate, dimethylsulfoxide and aromatic carboxyl groups). The genome consists of a single circular 2 628 784 bp chromosome encoding 2615 open reading frames (ORFs), which includes 2523 predicted protein‐encoding genes. Of these, 1834 genes (70.13%) have been assigned tentative functions, 665 (25.43%) matched genes of unknown function, and the remaining 24 (0.92%) had no database match. A total of 2384 (91.17%) of the ORFs in the M. thermoacetica genome can be grouped in orthologue clusters. This first genome sequence of an acetogenic bacterium provides important information related to how acetogens engage their extreme metabolic diversity by switching among different carbon substrates and electron donors/acceptors and how they conserve energy by anaerobic respiration. Our genome analysis indicates that the key genetic trait for homoacetogenesis is the core acs gene cluster of the Wood–Ljungdahl pathway.

Cognitive dysfunction induced by chronic administration of common cancer chemotherapeutics in rats - Gregory W. Konat; Michal Kraszpulski; Isaac James; Han-Ting Zhang; Jame Abraham (Metabolic Brain Disease, 2008)

Unique zinc mass in mandibles separates drywood termites from other groups of termites - Bronwen W. Cribb; Aaron Stewart; Han Huang; Rowan Truss; Barry Noller; Ronald Rasch; Myron P. Zalucki (The Science of Nature, 2008)

Insect mandibles—comparative mechanical properties and links with metal incorporation - Bronwen W. Cribb; Aaron Stewart; Han Huang; Rowan Truss; Barry Noller; Ronald Rasch; Myron P. Zalucki (The Science of Nature, 2007)

Assessment of Human Immune Response to Mutans Streptococcal Glucosyltransferase Peptides Selected by MHC Class II Binding Probability - Shauna Culshaw; Xiaozhe Han; Karen La Rosa; Jean W. Eastcott; Daniel J. Smith; Martin A. Taubman (International Journal of Peptide Research and Therapeutics, 2007)

Tobacco cultivars vary in induction of systemic resistance against Cucumber mosaic virus and growth promotion by Pseudomonas chlororaphis O6 and its gacS mutant - Choong-Min Ryu; Beom Ryong Kang; Song Hee Han; Song Mi Cho; Joseph W. Kloepper; Anne J. Anderson; Young Cheol Kim (European Journal of Plant Pathology, 2007)

Identification of the ADP-glucose pyrophosphorylase isoforms essential for starch synthesis in the leaf and seed endosperm of rice (Oryza sativa L.) - Sang-Kyu Lee; Seon-Kap Hwang; Muho Han; Joon-Seob Eom; Hong-Gyu Kang; Yulyi Han; Sang-Bong Choi; Man-Ho Cho; Seong Hee Bhoo; Gynheung An; Tae-Ryong Hahn; Thomas W. Okita; et al. (Plant Molecular Biology, 2007)

Changes of chemical and nutrient composition of porcine blood during fermentation by Aspergillus oryzae - J. Z. Wang; M. Zhang; F. Z. Ren; B. Z. Han; L. Wang; S. W. Chen; A. Humera (World Journal of Microbiology and Biotechnology, 2007)

Surveying sandy deserts and desertified lands in north‐western China by remote sensing - C. Z. Yan; T. Wang; Z. W. Han; Y. F. Qie (International Journal of Remote Sensing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Reusable immunomagnetic beads in an enzyme immunoassay - F. C. Han; J. Luo; H. F. Guo; W. H. Zhang; D. C. He; X. J. Yan (World Journal of Microbiology and Biotechnology, 2007)

Plasma protein advanced glycation end products, carboxymethyl cysteine, and carboxyethyl cysteine, are elevated and related to nephropathy in patients with diabetes - Ahmed A. Mostafa; Edward W. Randell; Sudesh C. Vasdev; Vicki D. Gill; Yingchun Han; Vereesh Gadag; Ahmed A. Raouf; Hala El Said (Molecular and Cellular Biochemistry, 2007)

Effect of Cadmium in Feed on Organs and Meat Colour of Growing Pigs - Y.-J. Tu; X.-Y. Han; Z.-R. Xu; Y.-Z. Wang; W.-F. Li (Veterinary Research Communications, 2007)

Approaching chickpea quantitative trait loci conditioning resistance to Ascochyta rabiei via comparative genomics - X. Y. Bian; R. Ford; T. R. Han; T. E. Coram; E. C. K. Pang; P. W. J. Taylor (Australasian Plant Pathology, 2007)

Volume density and distribution of mitochondria in harbor seal (Phoca vitulina) skeletal muscle - Rebecca R. Watson; Shane B. Kanatous; Daniel F. Cowan; Julie W. Wen; Violet C. Han; Randall W. Davis (Journal of Comparative Physiology B, 2006)

Intratumoral cytokines/chemokines/growth factors and tumor infiltrating dendritic cells: friends or enemies? - Michael R. Shurin; Galina V. Shurin; Anna Lokshin; Zoya R. Yurkovetsky; Dmitry W. Gutkin; Gurkamal Chatta; Hua Zhong; Baohui Han; Robert L. Ferris (Cancer and Metastasis Reviews, 2006)

Pacemaker currents modulated by C-type natriuretic peptide in interstitial cells of Cajal from murine small intestine - Y. Zhang; L. Hua Piao; X. Huang; Y. Fei Han; P. Zhao; L. Gao; Y. Kim; W. X. Xu (Journal of Physiology and Biochemistry, 2006)

Tests of Models for Saccade–Vergence Interaction using Novel Stimulus Conditions - Arun N. Kumar; Yanning H. Han; Robert F. Kirsch; Louis F. Dell’Osso; W. Michael King; R. John Leigh (Biological Cybernetics, 2006)

Genetic diversity of avian infectious bronchitis coronavirus strains isolated in China between 1995 and 2004 - S. W. Liu; Q. X. Zhang; J. D. Chen; Z. X. Han; X. Liu; L. Feng; Y. H. Shao; J. G. Rong; X. G. Kong; G. Z. Tong (Archives of Virology, 2006)

Rapid Determination of Mercury in Plant and Soil Samples Using Inductively Coupled Plasma Atomic Emission Spectroscopy, a Comparative Study - Fengxiang X. Han; W. Dean Patterson; Yunju Xia; B. B. Maruthi Sridhar; Yi Su (Water, Air, & Soil Pollution, 2006)

A genetic linkage map for azuki bean [Vigna angularis (Willd.) Ohwi & Ohashi] - O. K. Han; A. Kaga; T. Isemura; X. W. Wang; N. Tomooka; D. A. Vaughan (Theoretical and Applied Genetics, 2005)

Arsenic, Cadmium, Chromium, Cobalt, and Copper in Different Types of Chinese Tea - W.-Y. Han; Y.-Z. Shi; L.-F. Ma; J.-Y. Ruan (Bulletin of Environmental Contamination and Toxicology, 2005)

Inhibiting the Sexual Behavior of Female Cotton Bollworm Helicoverpa armigera - W. X. Dong; B. Y. Han; J. W. Du (Journal of Insect Behavior, 2005)

Mutational analysis of OGG1, MYH, MTH1 in FAP, HNPCC and sporadic colorectal cancer patients: R154H OGG1 polymorphism is associated with sporadic colorectal cancer patients - I.-J. Kim; J.-L. Ku; H. C. Kang; J.-H. Park; K.-A. Yoon; Y. Shin; H.-W. Park; S. G. Jang; S.-K. Lim; S. Y. Han; Y.-K. Shin; M. R. Lee; et al. (Human Genetics, 2004)

Genetic mapping of EST-derived microsatellites from the diploid Gossypium arboreum in allotetraploid cotton - Z.-G. Han; W.-Z. Guo; X.-L. Song; T.-Z. Zhang (Molecular Genetics and Genomics, 2004)

Experimental investigation of the mammary gland tumour phantom for multifrequency microwave radio-thermometers - J. W. Lee; S. M. Lee; K. S. Kim; W. T. Han; G. Yoon; L. A. Pasmanik; I. A. Ulyanichev; A. V. Troitsky (Medical & Biological Engineering & Computing, 2004)

Fine mapping of a malting-quality QTL complex near the chromosome 4H S telomere in barley - W. Gao; J. A. Clancy; F. Han; B. L. Jones; A. Budde; D. M. Wesenberg; A. Kleinhofs; S. E. Ullrich (Theoretical and Applied Genetics, 2004)

Identification and molecular modelling of a mutation in the motor head domain of myosin VIIA in a family with autosomal dominant hearing impairment (DFNA11) - Mirjam W. J. Luijendijk; Erwin van Wijk; Anne M. L. C. Bischoff; Elmar Krieger; Patrick L. M. Huygen; Ronald J. E. Pennings; Han G. Brunner; Cor W. R. J. Cremers; Frans P. M. Cremers; Hannie Kremer (Human Genetics, 2004)

Development of Oligonucleotide Primers for the Detection of Harmful Microcystis in Water - J.-E. Cho; S.-W. Bang; M.-S. Han (Bulletin of Environmental Contamination and Toxicology, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Determination of Semivolatile Compounds in Drinking Water by Tandem Mass Spectrometric Detection - L. Wang; Z. Huang; W. Zhou; C. Zhou; S. Han; A. Zhang; F. Feng; C. Liu (Bulletin of Environmental Contamination and Toxicology, 2003)

Molecular dissection of a dormancy QTL region near the chromosome 7 (5H) L telomere in barley - W. Gao; J. A. Clancy; F. Han; D. Prada; A. Kleinhofs; S. E. Ullrich (Theoretical and Applied Genetics, 2003)

Distribution and Sources of PAHs in Saemangeum Reclaimed Tidal Lands of Central Korea - J. Y. Cho; K. W. Han; J. H. Kim; J. K. Son; K. S. Yoon (Bulletin of Environmental Contamination and Toxicology, 2003)

The exotic American eel in Taiwan: ecological implications - Y.‐S. Han; C.‐H. Yu; H.‐T. Yu; C.‐W. Chang; I‐C. Liao; W.‐N. Tzeng (Journal of Fish Biology, 2002)
Six American eels Anguilla rostrata were identified in the Kaoping River of south‐western Taiwan by sequencing the mitochondrial cytochrome b gene ( mtCyt‐b ). This was the first record of an exotic eel species in the natural waters of Taiwan. The exotic eels may have been imported from North America at the elver stage for aquaculture and escaped from culture ponds.

An Assessment of the RAIM Performance of a Combined Galileo/GPS Navigation System Using the Marginally Detectable Errors (MDE) Algorithm - W. Y. Ochieng; K. F. Sheridan; K. Sauer; X. Han; P. A. Cross; S. Lannelongue; N. Ammour; K. Petit (GPS Solutions, 2002)

Morphology and sinking velocities of fecal pellets of copepod, molluscan, euphausiid, and salp taxa in the northeastern tropical Atlantic - Yoon W.; Kim S.; Han K. (Marine Biology, 2001)

Workshop on Bioanalytical Methods Validation for Macromolecules: Summary Report - Krys J. Miller; Ronald R. Bowsher; Abbie Celniker; Jacqueline Gibbons; Shalini Gupta; Jean W. Lee; Steve J. Swanson; Wendell C. Smith; Russell S. Weiner; Daan J. A. Crommelin; Ira Das; Binodh S. DeSilva; et al. (Pharmaceutical Research, 2001)

Origin of laminated diatom ooze in King George Basin sediments from Bransfield Strait, Antarctica - H. I. Yoon; B. K. Park; M. W. Han; B. K. Khim; Y. Kim; C. Y. Kang (Geosciences Journal, 2001)

Microsatellites from the South American Coruro, Spalacopus cyanus - James W. Schroeder; Rodney L. Honeycutt; Alejandro P. Rooney; George Han; Sabine Begall; Milton H. Gallardo (Molecular Ecology, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

Increased mRNAs for procollagens and key regulating enzymes in rat skeletal muscle following downhill running - Xiao-Yan Han; W. Wang; Satu O. A. Koskinen; Vuokko Kovanen; T. E. S. Takala; Jyrki Komulainen; Veikko Vihko; Philip C. Trackman (Pflügers Archiv - European Journal of Physiology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Expression of bvgAS of Bordetella pertussis represses flagellar biosynthesis of Escherichia coli - Y. W. Han; M. A. Uhl; Seog Joon Han; W. Shi (Archives of Microbiology, 1999)

Estimation of Target Hazard Quotients and Potential Health Risks for Metals by Consumption of Seafood in Taiwan - B.-C. Han; W. L. Jeng; R. Y. Chen; G. T. Fang; T. C. Hung; R. J. Tseng (Archives of Environmental Contamination and Toxicology, 1998)

Effects of Pluronic P85 Unimers and Micelles on Drug Permeability in Polarized BBMEC and Caco-2 Cells - Elena V. Batrakova; Huai-Yun Han; Donald W. Miller; Alexander V. Kabanov (Pharmaceutical Research, 1998)

Effects of Pluronic Block Copolymers on Drug Absorption in Caco-2 Cell Monolayers - Elena V. Batrakova; Huai-Yun Han; Valery Yu. Alakhov; Donald W. Miller; Alexander V. Kabanov (Pharmaceutical Research, 1998)

Influence of Different Fat Emulsion-Based Intravenous Formulations on the Pharmacokinetics and Pharmacodynamics of Propofol - Eugene H. Cox; Catherijne A. J. Knibbe; Victorine S. Koster; Mariska W. E. Langemeijer; Erica E. Tukker; Rogier Lange; Paul F. M. Kuks; Han J. M. Langemeijer; Loraine Lie-A-Huen; Meindert Danhof (Pharmaceutical Research, 1998)

Rock-Shells ( Thais clavigera ) as an Indicator of As, Cu, and Zn Contamination on the Putai Coast of the Black-Foot Disease Area in Taiwan - B. C. Han; W. L. Jeng; M. S. Jeng; L. T. Kao; P. J. Meng; Y. L. Huang (Archives of Environmental Contamination and Toxicology, 1997)

Chirp (2–7 kHz) echo characters in the Ulleung Basin - S. K. Chough; S. H. Lee; J. W. Kim; S. C. Park; D. G. Yoo; H. S. Han; S. H. Yoon; S. B. Oh; Y. B. Kim; G. G. Back (Geosciences Journal, 1997)

The longitudinal development of running economy in males and females aged between 13 and 27 years: The Amsterdam Growth and Health Study - Geertje A. M. Arins; Willem van Mechelen; Han C. G. Kemper; Jos W. R. Twisk; Willem van Mechelen (European Journal of Applied Physiology, 1997)

Cysteine ligand vibrations are responsible for the complex resonance Raman spectrum of azurin - Colin R. Andrew; Jane Han; Tanneke den Blaauwen; Gertie van Pouderoyen; Erik Vijgenboom; Gerard W. Canters; Thomas M. Loehr; J. Sanders-Loehr (JBIC Journal of Biological Inorganic Chemistry, 1997)

Effect of EHS matrix on expression of transgenes in HC11 cells - T. H. Lee; M. G. Baik; W. B. Im; C. S. Lee; Y. M. Han; S. J. Kim; K. K. Lee; Y. J. Choi (In Vitro Cellular & Developmental Biology - Animal, 1997)

Monitoring lead pollution near a storage battery recycling plant in Taiwan, Republic of China - C. -Y. Yeh; H. -Y. Chiou; R. -Y. Chen; K. -H. Yeh; W. -L. Jeng; B. -C. Han (Archives of Environmental Contamination and Toxicology, 1996)

Monitoring Lead Pollution Near a Storage Battery Recycling Plant in Taiwan, Republic of China - C.-Y. Yeh; H.-Y. Chiou; R.-Y. Chen; K.-H. Yeh; W.-L. Jeng, B.-C. Han (Archives of Environmental Contamination and Toxicology, 1996)

Effect of growth condition on enzymes of the citric acid cycle and the glyoxylate cycle in the photosynthetic bacterium Rhodopseudomonas palustris - J. H. Eley; K. Knobloch; T. -W. Han (Antonie van Leeuwenhoek, 1979)